Polyamide microparticles and method for producing the same
By controlling the ratio of the surface void ratio and specific surface area of the polyamide particles, or improving their spherical degree, the problem of large deviation of the dynamic friction coefficient during friction of existing polyamide particles is solved, and marine biodegradability is given, thereby improving sliding and tactile stability.
Patent Information
- Application Number
- CN202180078890.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-11-30
- Filing Date
- 2021-11-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2041-11-24
AI Technical Summary
The average deviation of the dynamic friction coefficient of the existing polyamide 4 particles when they rub against each other and the average deviation of the dynamic friction coefficient after time elapses, and lacks marine biodegradability.
By controlling the ratio of the proportion of the void on the particle surface to the specific surface area within the specified range, particles with a specific polyamide structure, or particles with a spherical degree of 96 or more are prepared, so as to achieve a small average deviation of the dynamic friction coefficient when the particles rub against each other and have marine biodegradability.
The average deviation of the dynamic friction coefficient when particles rub against each other is achieved is small, and the average deviation of the dynamic friction coefficient after time is also small, and it has marine biodegradability, which improves the sliding and tactile stability of the particles.
Smart Images

Figure CN116490543B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to polyamide microparticles and a method for producing the same. Background Art
[0002] Polyamide microparticles have excellent toughness and heat resistance and are therefore suitable for use in aircraft, automobiles, cosmetics, etc. Among them, in cosmetics, polyamide microparticles are used in powder foundations and the like because of their excellent sliding properties.
[0003] However, in recent years, there have been concerns about the impact of microplastics in the ocean on the ecosystem, and there is a growing trend to restrict the use of microplastics. Under such circumstances, marine biodegradable plastics that can be decomposed into substances existing in nature using the functions of microorganisms have attracted much attention. Polyamide microparticles are also required to have marine biodegradability, and development is being rapidly carried out to obtain such polyamide microparticles.
[0004] For example, Patent Document 1 discloses marine biodegradable polyamide 4 fine particles having a smooth surface and a sphericity of 95.
[0005] Patent Document 2 discloses marine biodegradable polyamide 4 fine particles which have medium sphericity and are porous.
[0006] Patent Document 3 discloses marine biodegradable polyamide 4 fine particles having a medium sphericity and low surface smoothness.
[0007] Patent Document 4 discloses marine biodegradable polyamide 4 microparticles having a medium sphericity and a large fluctuation in sphericity.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2020-100846
[0011] Patent Document 2: Japanese Patent Application Publication No. 2016-186068
[0012] Patent Document 3: International Publication No. 2017 / 195705
[0013] Patent Document 4: International Publication No. 2019 / 069799 Summary of the invention
[0014] Problems to be solved by the invention
[0015] However, Patent Document 1 does not provide a specific example of polyamide 4 microparticles having a smooth surface and a sphericity of 96 or more, and does not mention at all the average deviation of the kinetic friction coefficient when the microparticles obtained therefrom are rubbed against each other, or the average deviation of the kinetic friction coefficient after rubbing against each other over time (hereinafter, sometimes referred to as the kinetic friction coefficient after the passage of time).
[0016] In Patent Document 2, polyamide 4 microparticles are produced by contacting 2-pyrrolidone, which is a monomer of polyamide 4, with a compressible fluid to form microparticles, but the obtained polyamide 4 microparticles are hollow and porous microparticles with a medium degree of sphericity. As a result, the average deviation of the dynamic friction coefficient when the microparticles rub against each other and the average deviation of the dynamic friction coefficient after the passage of time become large, and the average deviation of each dynamic friction coefficient is insufficient from the viewpoint of the sliding property of the polyamide 4 microparticles.
[0017] In Patent Document 3, polyamide 4 microparticles are produced by dissolving polyamide 4 in hot water and reprecipitating the polyamide 4 microparticles, but the obtained polyamide 4 microparticles have low sphericity, large fluctuations in sphericity, and low surface smoothness. As a result, the average deviation of the dynamic friction coefficient when the microparticles rub against each other and the average deviation of the dynamic friction coefficient after a period of time become large, and the average deviations of the dynamic friction coefficients are insufficient from the viewpoint of the sliding properties of the polyamide 4 microparticles.
[0018] In Patent Document 4, polyamide 4 fine particles are produced by suspension polymerization of 2-pyrrolidone using a lithium salt in an aprotic solvent, but the obtained polyamide 4 fine particles have a medium sphericity, a large fluctuation in sphericity, and a rough surface. As a result, the average deviation of the dynamic friction coefficient when the fine particles are rubbed against each other and the average deviation of the dynamic friction coefficient after a period of time are both insufficient from the viewpoint of the sliding property of the polyamide 4 fine particles.
[0019] Therefore, the present invention has been made in view of the problems of the prior art, and an object of the present invention is to provide polyamide fine particles which have a small average variation in the coefficient of kinetic friction when the fine particles rub against each other and a small average variation in the coefficient of kinetic friction after a lapse of time, and which are marine biodegradable.
[0020] Means for solving problems
[0021] The inventors of the present application have repeatedly conducted in-depth studies in view of the above-mentioned problems, and as a result, have found that microparticles having a specific polyamide structure in which the ratio of the proportion of voids on the particle surface to the specific surface area of the particle surface is within a specified range, or microparticles having a specific polyamide structure with a sphericity of 96 or more are excellent in terms of the average deviation of the dynamic friction coefficient when the particles are rubbed against each other, are also excellent in terms of the average deviation of the dynamic friction coefficient after the elapse of time, and are marine biodegradable, thereby completing the present invention.
[0022] That is, in order to solve the above-mentioned problems and achieve the purpose, the polyamide microparticles according to the present invention are characterized in that the ratio r of the voids on the particle surface and the specific surface area of the particle surface measured by the BET method, that is, the BET specific surface area A BET The ratio (r / A BET ) is 6.0 or more and 100.0 or less, and is made of a polymer or copolymer having a repeating structural unit represented by the following chemical formula (1) as a main component.
[0023]
[0024] (In the chemical formula (1), x is an integer of 2 or more and 3 or less.)
[0025] In addition, the polyamide microparticles according to the present invention are characterized in that, in the above invention, the BET specific surface area A BET 0.8m 2 / g or more and 5.0m 2 / g or less.
[0026] Furthermore, the polyamide microparticles according to the present invention are characterized in that, in the above invention, the sphericity is 90 or more.
[0027] Furthermore, the polyamide fine particles according to the present invention are characterized in that, in the above invention, the impurity content is 0.50% by weight or less.
[0028] Furthermore, the polyamide microparticles according to the present invention are characterized in that, in the above invention, the volume average particle size is 0.1 μm or more and 100 μm or less.
[0029] Furthermore, the polyamide microparticles according to the present invention are characterized in that, in the above invention, the standard deviation of sphericity is 2.00 or less.
[0030] Furthermore, the polyamide fine particles according to the present invention are characterized in that, in the above invention, x in the chemical formula (1) is 3.
[0031] The polyamide microparticles according to the present invention are characterized in that, in the above invention, a temporal stability index calculated by the following mathematical formula is 0.60 or more, the temporal stability index being an index indicating stability with respect to a decrease in the touch of the polyamide microparticles after continuous rubbing over time.
[0032] Time stability index = 1 / (standard deviation of sphericity × (1 + impurity content))
[0033] (In the above mathematical formula, the standard deviation of sphericity is the standard deviation of sphericity of the polyamide microparticles. The impurity content is the impurity content of the polyamide microparticles.)
[0034] The method for producing polyamide microparticles according to the present invention is characterized in that the method is a method for producing polyamide microparticles using resin (A) and resin (B) as raw materials, wherein the resin (A) is a polymer or copolymer having a repeating structural unit represented by the following chemical formula (1) as a main component, and the resin (B) is an emulsion-forming resin capable of forming an emulsion with the resin (A) in a molten state, and the method comprises the following steps: an emulsion-forming step of melt-mixing the resin (A) and the resin (B) at a melting temperature not lower than their respective melting points to form an emulsion formed by the resin (A) and the emulsion forming step of melt-mixing the resin (A) and the resin (B) at a melting temperature not lower than their respective melting points to form an emulsion formed by the resin (B). The invention relates to a method for preparing a polyamide polyol according to the present invention, wherein the polyamide polyol is prepared by preparing a polyamide polyol. The method comprises the following steps: an emulsion in which particles of the resin (A) are dispersed in a resin (B); a fixing step in which a molten mixture of the resin (A) and the resin (B) forming the emulsion is cooled to a temperature below the crystallization temperature of the resin (A), thereby fixing the emulsion; and a recovery step in which the resin (B) is washed away using a washing solution which is a non-solvent for the resin (A), and polyamide particles made of the resin (A) are recovered. In the manufacturing method, the melt viscosity ratio of the resin (A) to the resin (B) at 270°C is greater than 4.3 and less than 125.0.
[0035]
[0036] (In the chemical formula (1), x is an integer of 2 or more and 3 or less.)
[0037] In addition, the method for producing polyamide microparticles according to the present invention is characterized in that, in the above-mentioned invention, the fixing step includes the following steps: a holding step of keeping the temperature of the molten mixture in a temperature range higher than the crystallization temperature of the resin (A) and lower than the melting point of the resin (A); and a cooling step of cooling the temperature of the molten mixture after being held in the temperature range to below the crystallization temperature of the resin (A).
[0038] Furthermore, the method for producing polyamide microparticles according to the present invention is characterized in that, in the above invention, in the maintaining step, the temperature of the molten mixture is maintained within the temperature range for 30 minutes to 10 hours.
[0039] In addition, the method for producing polyamide microparticles according to the present invention is characterized in that, in the above-mentioned invention, the fixing step includes the following steps: a holding step of holding the temperature of the molten mixture in a temperature range higher than the crystallization temperature of the resin (A) and lower than the melting point of the resin (A) for more than 1 second and less than 10 minutes; and a cooling step of cooling the temperature of the molten mixture after being held in the temperature range to below the crystallization temperature of the resin (A).
[0040] Furthermore, the method for producing polyamide microparticles according to the present invention is characterized in that, in the above invention, the emulsion forming step includes a temperature raising step of raising the temperature of the resin (A) and the resin (B) from room temperature to the melting temperature.
[0041] Furthermore, the method for producing polyamide microparticles according to the present invention is characterized in that, in the above invention, the resin (B) has a melt viscosity at 270° C. of 0.40 Pa·s or more and 5.00 Pa·s or less.
[0042] Furthermore, the method for producing polyamide microparticles according to the present invention is characterized in that, in the above invention, the resin (B) is polyethylene glycol.
[0043] In addition, the method for producing polyamide microparticles according to the present invention is characterized in that, in the above-mentioned invention, in the emulsion forming step, the resin (A) and the resin (B) are melt-mixed at the melting temperature of the melting point of the resin (A) + 5°C or more and 280°C or less.
[0044] The polyamide microparticles according to the present invention are characterized in that they have a sphericity of 96 or more and are made of a polymer or copolymer having a repeating structural unit represented by the following chemical formula (1) as a main component.
[0045]
[0046] (In the chemical formula (1), x is an integer of 2 or more and 3 or less.)
[0047] Furthermore, the polyamide fine particles according to the present invention are characterized in that, in the above invention, the impurity content is 0.50% by weight or less.
[0048] In addition, the polyamide microparticles according to the present invention are characterized in that, in the above invention, the specific surface area of the particle surface measured by the BET method, that is, the BET specific surface area A BET 5.0m 2 / g or less.
[0049] Furthermore, the polyamide microparticles according to the present invention are characterized in that, in the above invention, the volume average particle diameter is 0.1 μm or more and 100.0 μm or less.
[0050] Furthermore, the polyamide microparticles according to the present invention are characterized in that, in the above invention, the standard deviation of sphericity is 2.00 or less.
[0051] Furthermore, the polyamide fine particles according to the present invention are characterized in that, in the above invention, x in the chemical formula (1) is 3.
[0052] The polyamide microparticles according to the present invention are characterized in that, in the above invention, a temporal stability index calculated by the following mathematical formula is 0.60 or more, the temporal stability index being an index indicating stability with respect to a decrease in the touch of the polyamide microparticles after continuous rubbing over time.
[0053] Time stability index = 1 / (standard deviation of sphericity × (1 + impurity content))
[0054] (In the above mathematical formula, the standard deviation of sphericity is the standard deviation of sphericity of the polyamide microparticles. The impurity content is the impurity content of the polyamide microparticles.)
[0055] Effects of the Invention
[0056] According to the present invention, it is possible to provide polyamide fine particles having small average variation in the dynamic friction coefficient when fine particles are rubbed against each other and small average variation in the dynamic friction coefficient after a lapse of time and having marine biodegradability. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] [ Figure 1 ] Figure 1 This is a photograph obtained by observing the polyamide fine particles of Example 1 at 2,000 times magnification using a scanning electron microscope.
[0058] [ Figure 2 ] Figure 2 This is a photograph obtained by observing the polyamide fine particles of Example 1 at 10,000 times magnification using a scanning electron microscope.
[0059] [ Figure 3 ] Figure 3 This is a photograph obtained by observing the polyamide fine particles of Example 21 at 2,000 times magnification using a scanning electron microscope.
[0060] [ Figure 4 ] Figure 4 This is a photograph obtained by observing the polyamide fine particles of Example 21 at 10,000 times magnification using a scanning electron microscope. DETAILED DESCRIPTION
[0061] The preferred embodiments of the polyamide microparticles and the method for producing the same according to the present invention are described in detail below. The present invention is achieved by the inventions exemplified in the following embodiments 1 and 2, but is not limited to the embodiments 1 and 2 and can be implemented with various modifications according to the purpose and application.
[0062] <Implementation Method 1>
[0063] (Polyamide microparticles)
[0064] The polyamide fine particles according to the first embodiment of the present invention are smooth-surfaced, highly spherical polyamide fine particles characterized by having a sphericity of 96 or more and being made of a polymer or copolymer having a repeating structural unit represented by the following chemical formula (1) as a main component.
[0065]
[0066] (In the chemical formula (1), x is an integer of 2 or more and 3 or less.)
[0067] First, the structure and morphology of the polyamide microparticles (hereinafter sometimes referred to as polyamide microparticles (P1)) constituting the first embodiment of the present invention are described. The polyamide microparticles (P1) are microparticles made of a polymer or copolymer having the structural unit represented by the above chemical formula (1) as a main repeating structural unit. In the above chemical formula (1), x is 2 or 3. When x is not 2 or 3, the polyamide microparticles (P1) do not have sufficient marine biodegradability. It should be noted that from the perspective of the excellent operability of the polyamide microparticles (P1), x is preferably 3. In addition, the polyamide microparticles (P1) may also contain a cross-linked structure or a branched structure within the range that does not impair the effect of the invention involved in the first embodiment.
[0068] The sphericity of polyamide particles (P1) is 96 or more. In polyamide particles with a sphericity less than 96, the average deviation of the coefficient of kinetic friction becomes larger, and as a result, the touch comfort when touching the polyamide particles is not good. In addition, if the polyamide particles with a sphericity less than 96 are continuously rubbed, the polyamide particles are agglomerated and entangled with each other, so that the average deviation of the coefficient of kinetic friction after the passage of time is also increased, and as a result, the sense of touch when the polyamide particles are continuously used is deteriorated. Therefore, when polyamide particles are used for cosmetics and coatings, a smooth sense of touch cannot be given. From these viewpoints, the sphericity of polyamide particles (P1) is more than 96 as described above, preferably more than 97, more preferably more than 98, and further preferably 100. In addition, the upper limit of the sphericity of polyamide particles (P1) is 100.
[0069] The standard deviation of the sphericity of polyamide particles (P1) is preferably less than 2.00. If the standard deviation of the sphericity is less than 2.00, when the polyamide particles (P1) are continuously rubbed, it is not easy to cause the deterioration of the touch comfort caused by agglomeration and entanglement, and the average deviation of the dynamic friction coefficient after the time elapses becomes smaller. Thus, even when the polyamide particles (P1) are used for the purposes of cosmetics and coatings, a smooth touch can be given, so it is preferred. The standard deviation of the sphericity of polyamide particles (P1) is more preferably less than 1.75, further preferably less than 1.50, particularly preferably less than 1.30, and particularly preferably less than 1.10. In addition, in polyamide particles (P1), the lower limit of the standard deviation of sphericity is theoretically 0.
[0070] It should be noted that the sphericity of the polyamide microparticles (P1) and the standard deviation of the sphericity are determined, for example, by randomly observing 50 polyamide microparticles (P1) from photographs of the polyamide microparticles (P1) taken at a magnification of 2,000 times or more and 5,000 times or less using a scanning electron microscope, and by the observed short diameter and long diameter of the polyamide microparticles (P1), respectively, according to the following mathematical formula (1) and mathematical formula (2). In addition, the value of the sphericity is expressed as an integer by rounding off. For example, when the calculated sphericity value is 99.5 or more, the sphericity of the polyamide microparticles (P1) is expressed as 100.
[0071]
[0072] (T: sphericity (average value), a i : The major diameter of each particle, b i : the short diameter of each particle, n: the number of particles measured)
[0073]
[0074] (s: standard deviation of sphericity, T i : sphericity of each particle, T: sphericity (average value), n: number of measurements)
[0075] In the above equations (1) and (2), the number of measurements n is the number of measurements of the sphericity, minor axis, and major axis of the target microparticles. For example, in the first embodiment of the present invention, the number of measurements n of the polyamide microparticles (P1) is set to, for example, n=50.
[0076] The volume average particle size of the polyamide microparticles (P1) is preferably within a range of 0.1 μm or more and 100.0 μm or less. If the volume average particle size of the polyamide microparticles (P1) is 100.0 μm or less, the tactile feel when touching the polyamide microparticles (P1) is excellent, and the average deviation of the dynamic friction coefficient after the measurement is just started is small, so it is preferred. It should be noted that the so-called dynamic friction coefficient after the measurement is just started is the dynamic friction coefficient after the measurement of the object microparticles (polyamide microparticles (P1) in Embodiment 1), that is, the dynamic friction coefficient in the stage where the microparticles begin to rub against each other. As the upper limit of the volume average particle size of the polyamide microparticles (P1), it is more preferably 50.0 μm or less, further preferably 30.0 μm or less, particularly preferably 15.0 μm or less, more preferably 13.0 μm or less, and particularly preferably 10.0 μm or less. In addition, if the volume average particle size of the polyamide fine particles (P1) is 0.1 μm or more, it is difficult for the polyamide fine particles (P1) to aggregate with each other, the reduction in touch caused by aggregation can be suppressed, and the average deviation of the dynamic friction coefficient immediately after the measurement and after the passage of time becomes small, which is preferred. The lower limit of the volume average particle size of the polyamide fine particles (P1) is more preferably 0.3 μm or more, further preferably 0.5 μm or more, and particularly preferably 1.0 μm or more.
[0077] The particle size distribution index representing the particle size distribution of the polyamide microparticles (P1) is preferably 3.0 or less. If the particle size distribution index is 3.0 or less, the fluidity is excellent and the sliding property is improved in the applications such as coatings and cosmetics using the polyamide microparticles (P1). The particle size distribution index of the polyamide microparticles (P1) is more preferably 2.0 or less, further preferably 1.5 or less, particularly preferably 1.3 or less, and particularly preferably 1.2 or less. In addition, the lower limit of the particle size distribution index of the polyamide microparticles (P1) is theoretically 1.0.
[0078] It should be noted that the volume average particle size and number average particle size of the polyamide microparticles (P1) refer to the volume average particle size and number average particle size measured by a laser diffraction / scattering particle size distribution meter, respectively. In addition, the particle size distribution index of the polyamide microparticles (P1) can be calculated by the following mathematical formula (3) using the values of the volume average particle size and number average particle size obtained as described above.
[0079] Particle size distribution index = volume average particle size / number average particle size ... mathematical formula (3)
[0080] BET specific surface area A of polyamide microparticles (P1) BET Preferably 5.0m 2 The surface smoothness of the polyamide microparticles (P1) can be determined by the BET specific surface area A based on gas adsorption. BETThe polyamide fine particles (P1) do not have a hollow structure, and the smoother the surface of the polyamide fine particles (P1), the greater the BET specific surface area A. BET The value becomes smaller. BET specific surface area A BET The smaller the value of is, the less deterioration of the touch comfort caused by the aggregation and entanglement of the polyamide fine particles (P1) will occur when the polyamide fine particles (P1) are continuously rubbed, and the smaller the average deviation of the dynamic friction coefficient after the passage of time. BET From the viewpoint of the comfort of touch when the polyamide fine particles (P1) are continuously rubbed, the BET specific surface area A of the polyamide fine particles (P1) is preferably BET The upper limit value is preferably 5.0 m 2 / g or less, more preferably 4.0m 2 / g or less, more preferably 3.0m 2 / g or less, and more preferably 2.0m 2 / g or less, particularly preferably 1.0 m 2 / g or less.
[0081] It should be noted that the BET specific surface area A BET The specific surface area of the particle surface measured by the BET method can be measured, for example, in accordance with Japanese Industrial Standards (JIS standards) JIS R1626 (1996) "Method for measuring specific surface area by gas adsorption BET method".
[0082] The weight average molecular weight of the polyamide microparticles (P1) is preferably 2,000 or more and 2,000,000 or less. If the weight average molecular weight is 2,000 or more, when the polyamide microparticles (P1) are continuously rubbed, the deterioration of the touch comfort caused by the agglomeration and entanglement of the polyamide microparticles (P1) is not easy to occur, and the average deviation of the dynamic friction coefficient after the time has passed becomes smaller, so it is preferred. As the lower limit of the weight average molecular weight of the polyamide microparticles (P1), it is more preferably 3,000 or more, further preferably 4,000 or more, and particularly preferably 5,000 or more. If the weight average molecular weight of the polyamide microparticles (P1) is 2,000,000 or less, the average deviation of the dynamic friction coefficient after the measurement is just started becomes smaller, and the touch when the polyamide microparticles (P1) are rubbed against each other is excellent, so it is preferred. The upper limit of the weight average molecular weight of the polyamide fine particles (P1) is more preferably 1,000,000 or less, further preferably 500,000 or less, particularly preferably 100,000 or less, particularly preferably 50,000 or less, and still more preferably less than 30,000.
[0083] It should be noted that the weight average molecular weight can be calculated, for example, by gel permeation chromatography (hereinafter, sometimes referred to as GPC). Specifically, a solvent in which the compound can be dissolved, such as hexafluoroisopropanol, can be used as a mobile phase, polymethyl methacrylate (PMMA) can be used as a standard substance, and the column and the solvent can be matched. For example, when hexafluoroisopropanol is used, at least one of "Shodex GPC HFIP-806M" and "Shodex GPC HFIP-LG" manufactured by Shimadzu Corporation is used, and a differential refractometer is used as a detector to measure the weight average molecular weight.
[0084] The weight of the entire polyamide microparticle (P1) is set to 100.00% by weight, and the impurity content of the polyamide microparticle (P1) is preferably 0.50% by weight or less. In the present invention, the impurities contained refer to: the resin (B) described later, the catalyst, initiator, etc. used in the manufacture of the resin (A) described later, and the components other than the resin (A) contained in the polyamide microparticle (P1) described later. If the impurity content is less than 0.50% by weight, when the polyamide microparticle (P1) is continuously rubbed, it is not easy to cause the deterioration of the touch comfort caused by the agglomeration and entanglement of the polyamide microparticle (P1), and the average deviation of the dynamic friction coefficient after the passage of time becomes smaller. Therefore, even when the polyamide microparticle (P1) is used for cosmetics and coatings, it can also give a smooth touch, so it is preferred. The impurity content is more preferably less than 0.30% by weight, and particularly preferably less than 0.10% by weight. In addition, the lower limit of the impurity content is theoretically 0.00% by weight.
[0085] It should be noted that the impurity content can be determined by measuring the contents of organic matter and inorganic matter other than the resin (A) described later contained in the polyamide microparticles (P1), and the total amount thereof can be obtained as the impurity content. The content of organic matter can be obtained by analyzing using methods such as NMR, FT-IR, GC-MS, and liquid chromatography alone or in combination, and the content of inorganic matter can be determined by, for example, the ash content when the polyamide microparticles are ashed at 550°C.
[0086] The temporal stability index of the polyamide microparticles (P1) calculated by the following mathematical formula (4) is preferably 0.60 or more. The temporal stability index is an index indicating the stability of the microparticles (polyamide microparticles (P1) in Embodiment 1) after continuous friction over time due to the reduction of the sense of touch caused by agglomeration, entanglement, etc. The larger the value of the temporal stability index, the more it means that even if the microparticles as the object are continuously rubbed for a long time, the excellent sense of touch of the microparticles can be maintained. For example, even when the polyamide microparticles (P1) are used in cosmetic applications, the excellent sense of touch of the polyamide microparticles (P1) can be maintained for a long time. In particular, when the temporal stability index is 0.60 or more, when the polyamide microparticles (P1) are continuously rubbed, it is not easy to cause the deterioration of the touch comfort caused by the agglomeration and entanglement of the polyamide microparticles (P1), and the average deviation of the dynamic friction coefficient after the time has passed becomes smaller, so it is preferred. As the lower limit of the temporal stability index of the polyamide microparticles (P1), it is more preferably 0.70 or more, and more preferably 0.80 or more.
[0087] Temporal stability index = 1 / (s×(impurity content+1))…Mathematical formula (4)
[0088] In the above mathematical formula (4), s is the standard deviation of the sphericity of the polyamide fine particles (P1). The standard deviation of the sphericity can be calculated by the above mathematical formula (2). In addition, the impurity content is the impurity content of the polyamide fine particles (P1).
[0089] In addition, the polyamide microparticles (P1) have marine biodegradability. The so-called marine biodegradability is the property of being decomposed by microorganisms in the sea. As an indicator of marine biodegradability, in the present invention, the case where more than 10% is decomposed after 2 months from the start of the test according to JIS K6955 (2006) is considered to have marine biodegradability. From the viewpoint of showing good marine biodegradability of polyamide microparticles (P1), the lower limit of the marine biodegradability of polyamide microparticles (P1) is preferably more than 15%, more preferably more than 20%, and further preferably more than 30%. In addition, if the marine biodegradability is too high, the period during which the polyamide microparticles (P1) are used as a product (the product life of the polyamide microparticles (P1)) can be shortened. Therefore, the upper limit of the marine biodegradability of polyamide microparticles (P1) is preferably less than 90%, more preferably less than 80%, and further preferably less than 70%.
[0090] (Method for producing polyamide microparticles)
[0091] Next, the method for producing polyamide microparticles according to the first embodiment of the present invention will be described in detail. The polyamide microparticles (P1) described above can be produced by the production method according to the first embodiment of the present invention.
[0092] In detail, the method for producing polyamide microparticles according to Embodiment 1 of the present invention (hereinafter, sometimes referred to as the production method of Embodiment 1) is a method for producing polyamide microparticles (P1) using resin (A) and resin (B) as raw materials, wherein the resin (A) is a polymer or copolymer having a repeating structural unit represented by the above-mentioned chemical formula (1) as a main component, and the resin (B) is an emulsion-forming resin that can form an emulsion with the resin (A) in a molten state. The production method of Embodiment 1 includes an emulsion forming step, a fixation step, and a recovery step. The emulsion forming step is a step of melt-mixing the resin (A) and the resin (B) at a melting temperature that is a temperature above their respective melting points to form an emulsion in which particles of the resin (A) are dispersed in the resin (B). The fixation step is a step of cooling the molten mixture of the resin (A) and the resin (B) that forms the above-mentioned emulsion to below the crystallization temperature of the resin (A) to fix the above-mentioned emulsion. The recovery step is a step of washing away the resin (B) in the fixed molten mixture using a washing solution that is a non-solvent for the resin (A) to recover polyamide microparticles made of the resin (A). In addition, in the production method of the first embodiment, the melt viscosity ratio of the resin (A) to the resin (B) at 270° C. is 4.3 or more and 125.0 or less.
[0093] [Resin (A)]
[0094] The resin (A) is a polymer resin used in the production method of the first embodiment as a raw material of the polyamide fine particles (P1), and more specifically, is a polymer or copolymer having the structural unit represented by the chemical formula (1) as a main repeating structural unit.
[0095]
[0096] (In the chemical formula (1), x is an integer of 2 or more and 3 or less.)
[0097] In the structural unit of the resin (A), x is 2 or 3. When x is not 2 or 3, the polyamide fine particles (P1) produced from the resin (A) do not have sufficient marine biodegradability. From the viewpoint of excellent handling properties of the polyamide fine particles (P1), x is preferably 3. In addition, the resin (A) may contain a crosslinked structure or a branched structure within a range that does not impair the effects of the invention according to the first embodiment.
[0098] In addition, in embodiment 1, the melt viscosity of resin (A) at 270°C is not particularly limited, and is preferably 0.02 Pa·s or more and 1.00 Pa·s or less. In order to disperse in the resin (B) described later in a particle form to form an emulsion with the resin (B), the resin (A) preferably has a certain degree of viscosity. As the lower limit of the melt viscosity of such resin (A) at 270°C, it is preferably 0.02 Pa·s or more, more preferably 0.03 Pa·s or more, and even more preferably 0.04 Pa·s or more. In addition, from the viewpoint that the emulsion particle size does not become too large when forming an emulsion of resin (A) and resin (B) and can maintain a spherical shape, the upper limit of the melt viscosity of resin (A) at 270°C is preferably 1.00 Pa·s or less, more preferably 0.80 Pa·s or less, even more preferably 0.50 Pa·s or less, and particularly preferably 0.30 Pa·s or less.
[0099] It should be noted that the melt viscosity of the resin (A) can be measured using a rheometer. Specifically, the complex viscosity of the resin (A) measured at a temperature of 270°C and a frequency of 1 Hz 5 minutes after the start of the measurement can be obtained as the melt viscosity of the resin (A).
[0100] The resin (A) used in the manufacturing method of embodiment 1 can be manufactured using a known polymerization method. That is, in the manufacture of resin (A), the polycondensation reaction of amino acids such as 4-aminobutyric acid and 3-aminopropionic acid, the ring-opening polymerization of lactams such as 2-pyrrolidone and 2-azetidinone, etc. can be used. As the ring-opening polymerization, for example, ring-opening polymerization, anionic ring-opening polymerization, etc., carried out by hydrolysis using water can be cited. As the anionic ring-opening polymerization, for example, anionic ring-opening polymerization can be cited using an alkali metal such as sodium, potassium, sodium hydroxide, potassium hydroxide, sodium hydride, potassium hydride, sodium methoxide, potassium methoxide, sodium ethoxide, potassium ethoxide, sodium tert-butoxide, potassium tert-butoxide, sodium pyrrolidone, potassium pyrrolidone, hydroxides, hydrides, salts, butyl lithium, butyl magnesium and other organometallic compounds of alkali metals such as butyl lithium, butyl magnesium can be used. Resin (A) can be manufactured by the above-mentioned polycondensation reaction and ring-opening polymerization. In the case of utilizing anionic ring-opening polymerization in the manufacture of resin (A), it is preferred to further add a polymerization accelerator from the perspective of improving yield, etc. As the polymerization accelerator, a known polymerization accelerator can be used, and for example, N-acyl-caprolactam, N-acyl-pyrrolidone, N-acyl-azetidinone, etc. can be cited. It should be noted that polymerization can be carried out in a solvent, or bulk polymerization can be carried out without using a solvent. When using a solvent, as long as polymerization is carried out, there is no particular restriction on the solvent, and solution polymerization can be carried out in a good solvent for resin (A), or suspension polymerization can be carried out in a non-solvent for resin (A).
[0101] In addition, the copolymerization component of the resin (A) is not particularly limited as long as it does not impair the effects of the present invention, and examples thereof include amino acids such as 3-aminopropionic acid, 2-aminopropionic acid, alanine, glycine, and valine, and lactones such as β-propiolactone, γ-butyrolactone, δ-valerolactone, and ε-caprolactone. These components are preferred as the copolymerization components of the resin (A) from the viewpoint of being able to impart added value such as moisturizing properties when the polyamide fine particles (P1) are made into cosmetics without impairing the marine biodegradability of the polyamide fine particles (P1).
[0102] [Resin (B)]
[0103] Resin (B) is a polymer resin used in the manufacturing method of embodiment 1 together with the above-mentioned resin (A) as a raw material of polyamide microparticles (P1). Specifically, it is an emulsion-forming resin that can form a polymer / polymer emulsion with the above-mentioned resin (A) in a molten state. The so-called polymer / polymer emulsion is an emulsion in which two resins that are incompatible with each other in a molten state are used, and one of the two resins is dispersed in a spherical state in the other resin. In the manufacturing method of embodiment 1, the polymer / polymer emulsion is an emulsion in which the resin (A) in the form of particles (spherical) is dispersed in the resin (B). Such a polymer / polymer emulsion can be formed by making the interfacial tension and melt viscosity of the two resins satisfy a specific balance.
[0104] The resin (B) in the manufacture method of embodiment 1 is not particularly limited as long as it is an emulsion-forming resin that forms a polymer / polymer emulsion with the above-mentioned resin (A) in a molten state. As a specific example of such an emulsion-forming resin, polyethylene glycol, polypropylene glycol, polybutylene glycol, polypentanediol, polyhexylene glycol, and the alkyl ether bodies formed by chain-sealing the hydroxyl groups at one or both ends thereof with methyl, ethyl, propyl, isopropyl, butyl, hexyl, octyl, decyl, dodecyl, hexadecyl, octadecyl, etc., and the alkylphenyl ether bodies formed by chain-sealing with octylphenyl, etc., etc. In particular, from the viewpoint that water can be used as a cleaning solvent when the resin (B) is cleaned and removed in the recovery process described later after forming a polymer / polymer emulsion with the above-mentioned resin (A), and that it is economically and preferably environmentally excellent, resin (B) is preferably selected from more than one of the group consisting of polyethylene glycol, polypropylene glycol, polybutylene glycol, and their alkyl ether bodies. In addition, from the viewpoint that it can form a good polymer / polymer emulsion with the above-mentioned resin (A) in a molten state, and the obtained polyamide microparticles (P1) become microparticles with high sphericity and small standard deviation of sphericity, the resin (B) is most preferably polyethylene glycol. In addition, as the resin (B), two or more of the above-mentioned multiple emulsion-forming resins may be used simultaneously within the scope of not impairing the effect of the present invention.
[0105] In addition, in the manufacturing method of embodiment 1, the melt viscosity of the resin (B) at 270°C is preferably 0.40 Pa·s or more and 5.00 Pa·s or less. In order to form a polymer / polymer emulsion with the above-mentioned resin (A) in a molten state, the resin (B) must have a moderate viscosity. From this point of view, the above-mentioned melt viscosity of the resin (B) is preferably 0.40 Pa·s or more and 5.00 Pa·s or less. From the viewpoint that the particle size of the polyamide microparticles (P1) will not be excessively coarsened, the touch comfort when touching the polyamide microparticles (P1) is excellent, and the average deviation of the dynamic friction coefficient after the initial measurement becomes small, the lower limit of the melt viscosity of the resin (B) at 270°C is preferably 0.40 Pa·s or more, more preferably 0.60 Pa·s or more, and even more preferably 0.80 Pa·s or more. In addition, from the viewpoint that the particle size of the polyamide microparticles (P1) does not become too small, the deterioration of the touch comfort when touching the polyamide microparticles (P1) caused by agglomeration etc. can be suppressed, and the average deviation of the dynamic friction coefficient after the lapse of time can be reduced, the upper limit of the melt viscosity of the resin (B) at 270°C is preferably 5.00 Pa·s or less, more preferably 4.00 Pa·s or less, further preferably 3.00 Pa·s or less, and particularly preferably 2.00 Pa·s or less.
[0106] In addition, in the manufacturing method of embodiment 1, the melt viscosity ratio of resin (A) to resin (B) at 270°C is 4.3 or more and 125.0 or less. In this manufacturing method, resin (A) and resin (B) form a polymer / polymer emulsion in a molten state, which enables the formation of polyamide microparticles (P1) having excellent surface smoothness, high sphericity, and less fluctuation of sphericity. Therefore, from the perspective of making polyamide microparticles (P1) with marine biodegradability, in which the average deviation of the coefficient of kinetic friction when the microparticles rub against each other is small and the average deviation of the coefficient of kinetic friction after time has passed is also small, the formation of the polymer / polymer emulsion of the above-mentioned resin (A) and resin (B) is necessary. Although the principle cannot be explained in detail, only when the resin (A) and resin (B) whose melt viscosity ratio satisfies the condition of 4.3 or more and 125.0 or less are melt-mixed, the interfacial tension and melt viscosity of these resins (A) and resin (B) are kept within a suitable range, and as a result, the characteristics of the polyamide microparticles (P1) can be obtained.
[0107] When the melt viscosity ratio of resin (A) to resin (B) at 270°C is less than 4.3, the particle size of the emulsion of resin (A) in resin (B) becomes too large in the molten state of resin (A) and resin (B), so that a polymer / polymer emulsion of resin (A) and resin (B) cannot be formed. From the viewpoint of improving the smoothness of the polyamide microparticles (P1) when touched, reducing the foreign body feeling, and reducing the average deviation of the dynamic friction coefficient immediately after the measurement, the melt viscosity ratio is preferably 10.0 or more, more preferably 15.0 or more, and even more preferably 20.0 or more.
[0108] On the other hand, when the melt viscosity ratio of the resin (A) to the resin (B) at 270° C. is greater than 125.0, the particle size of the emulsion of the resin (A) formed in the resin (B) becomes excessively small, and the stability of the emulsion of the resin (A) and the resin (B) is lost, so that the polyamide fine particles (P1) cannot be obtained. From the viewpoint of improving the touch comfort when the polyamide fine particles (P1) are continuously rubbed and reducing the average deviation of the dynamic friction coefficient after the passage of time, the melt viscosity ratio is preferably 100.0 or less, more preferably 75.0 or less, further preferably 50.0 or less, and particularly preferably 40.0 or less.
[0109] It should be noted that the melt viscosity of the above-mentioned resin (B) can be measured using a rheometer. Specifically, the value of the complex viscosity of the resin (B) measured 5 minutes after the start of the measurement under the conditions of a temperature of 270°C and a frequency of 1 Hz can be obtained as the above-mentioned melt viscosity of the resin (B). In addition, the melt viscosity ratio of the resin (A) to the resin (B) at 270°C can be calculated by the following mathematical formula (5) using the obtained melt viscosities of the resin (A) and the resin (B).
[0110] Melt viscosity ratio = melt viscosity of resin (B) / melt viscosity of resin (A) ... Mathematical formula (5)
[0111] [Emulsion Formation Step]
[0112] The manufacturing method of the first embodiment includes an emulsion forming step as described above. The emulsion forming step is a step of melt-mixing the resin (A) and the resin (B) at a temperature (melting temperature) above their respective melting points to form a polymer / polymer emulsion of the resin (A) and the resin (B). Hereinafter, the emulsion forming step in the manufacturing method of the first embodiment is referred to as an emulsion forming step (ST1).
[0113] The melting temperature in the emulsion forming step (ST1) is the temperature when the resin (A) and the resin (B) are melt-mixed. It is not particularly limited as long as it is above the melting points of these resins (A) and resins (B), and can be selected according to the type of resin (A). From the viewpoint of producing polyamide microparticles (P1) with higher sphericity and smaller standard deviation of sphericity, the above-mentioned melting temperature is preferably a temperature of the melting point of the resin (A) + 5°C or more. On the other hand, from the viewpoint of being able to suppress the decomposition of the resin (A) in a state of being melt-mixed with the resin (B) and being able to form a stable polymer / polymer emulsion of the resin (A) and the resin (B), and further improving the sphericity of the obtained polyamide microparticles (P1), the upper limit of the above-mentioned melting temperature is preferably 280°C or less. From the viewpoint of further improving the sphericity, the upper limit of the above-mentioned melting temperature is more preferably 270°C or less. In addition, the melt mixing time of the resin (A) and the resin (B) in the emulsion forming step (ST1) can be about 1 minute to 10 hours.
[0114] It should be noted that the melting points of the resin (A) and the resin (B) used in the emulsion forming step (ST1) can be measured by a differential scanning calorimeter (hereinafter, sometimes referred to as DSC). For example, the resin (A) can be heated from 30°C at a rate of 20°C / min under a nitrogen atmosphere to an endothermic peak showing the melting point of polyamide, and then maintained for 1 minute. The resin (A) after being maintained for 1 minute is cooled to 30°C at a rate of 20°C / min, and the temporarily cooled resin (A) is further heated at a rate of 20°C / min, and the top of the endothermic peak at this time is measured as the melting point of the resin (A). The melting point of the resin (B) can also be measured in the same manner as the melting point of the above-mentioned resin (A).
[0115] In addition, the emulsion forming step (ST1) preferably includes a heating step of heating the resin (A) and the resin (B) as raw materials from room temperature to the above-mentioned melting temperature. Although the detailed principle is not clear, by heating the resin (A) and the resin (B) as raw materials from room temperature, it becomes possible to form a more uniform and shape-stable polymer / polymer emulsion of the resin (A) and the resin (B). Therefore, from the viewpoint that the sphericity of the obtained polyamide particles (P1) is high and the standard deviation of the sphericity becomes small, the emulsion forming step (ST1) preferably includes the above-mentioned heating step.
[0116] In the emulsion forming step (ST1), the melt mixing ratio of the resin (A) and the resin (B) can be exemplified as 25:75 to 75:25 using the mass ratio of these resins (A) and resins (B) ((A):(B)). If the melt mixing ratio of the resin (A) and the resin (B) is within the above range, the interfacial tension and melt viscosity of the melt-mixed resins (A) and (B) can be balanced within a suitable range, and a polymer / polymer emulsion of the resins (A) and (B) can be formed. Therefore, the melt mixing ratio of the resin (A) and the resin (B) in the emulsion forming step (ST1) is preferably within the above range. From the viewpoint of improving the sphericity of the obtained polyamide microparticles (P1), the melt mixing ratio is more preferably 30:70 to 75:25, further preferably 40:60 to 75:25, and particularly preferably 50:50 to 75:25.
[0117] In addition, in the emulsion forming step (ST1), fine particles can be produced even if the molten mixture of resin (A) and resin (B) is not stirred, but the molten mixture may be stirred in order to uniformly control the volume average particle size and particle size distribution of the obtained polyamide particles (P1). As a stirring device, known devices such as stirring blades, melt kneading machines, and homogenizers can be used. For example, as stirring blades, propellers, paddles, flat plates, turbines, cones, anchors, screws, spirals, etc. can be cited. The stirring speed depends on the type and melt viscosity of the resin (B), but from the perspective of being able to uniformly transfer heat even in a large device and preventing the liquid from adhering to the wall surface and changing the mixing ratio, it is preferably in the range of 0 to 2,000 rpm. As the lower limit of the stirring speed, it is more preferably 10 rpm or more, more preferably 30 rpm or more, and particularly preferably 50 rpm or more. As the upper limit of the stirring speed, it is more preferably 1,600 rpm or less, more preferably 1,200 rpm or less, and particularly preferably 800 rpm or less.
[0118] In the manufacturing method of embodiment 1, in the emulsion forming step (ST1), additives may be added and melt-mixed within a range that does not damage the effect of the present invention. Examples of the additives include surfactants, dispersants, antioxidants, heat stabilizers, weathering agents, lubricants, pigments, dyes, plasticizers, antistatic agents, flame retardants, etc. Two or more of these additives may be used.
[0119] The amount of the additive can be appropriately selected, preferably 0.00% by weight or more and 15.00% by weight or less relative to the total of 100.00% by weight of the resin (A) and the resin (B). From the viewpoint of fully exhibiting the effect of the additive, the lower limit of the amount of the additive is more preferably 0.01% by weight or more, further preferably 0.05% by weight or more, and particularly preferably 0.10% by weight or more relative to the total of 100.00% by weight of the resin (A) and the resin (B). In addition, from the viewpoint of reducing the impurity content of the obtained polyamide microparticles (P1), the upper limit of the amount of the additive is more preferably 10.00% by weight or less, further preferably 5.00% by weight or less, particularly preferably 3.00% by weight or less, and particularly preferably 1.00% by weight or less relative to the total of 100.00% by weight of the resin (A) and the resin (B).
[0120] [Immobilization process]
[0121] The manufacturing method of the first embodiment includes a fixing step as described above. The fixing step is a step of cooling the molten mixture of the resin (A) and the resin (B) obtained in the emulsion forming step (ST1) to form a polymer / polymer emulsion to a temperature below the crystallization temperature of the resin (A), thereby fixing the polymer / polymer emulsion (i.e., making it non-flowing). Hereinafter, the fixing step in the manufacturing method of the first embodiment is referred to as a fixing step (ST2).
[0122] The cooling method of the molten mixture of resin (A) and resin (B) in the fixing step (ST2) is not limited as long as it is within the scope that does not impair the effect of the invention involved in the first embodiment, and the following methods can be exemplified: a method of discharging the molten mixture into a cleaning solution described later and rapidly cooling it in the cleaning solution; a method of adding a cleaning solution described later into a mixing device after mixing the molten mixture and rapidly cooling the molten mixture; a method of air-cooling the molten mixture in a mixing device and then discharging or transferring the molten mixture to a cleaning solution described later; a method of discharging the molten mixture into the atmosphere for cooling and then transferring the molten mixture to a cleaning solution described later, etc. It should be noted that the cooling rate of the molten mixture is not particularly limited as long as it is within the scope that does not impair the effect of the invention involved in the first embodiment, and it can be rapid cooling or natural cooling.
[0123] In addition, the fixing step (ST2) preferably includes the following steps: a holding step of keeping the temperature of the molten mixture of the resin (A) and the resin (B) within a predetermined temperature range; and a cooling step of cooling the molten mixture after the holding step. The holding step is to keep the temperature of the molten mixture t 混合物The step of maintaining the molten mixture in a temperature range higher than the crystallization temperature of the resin (A) and lower than the melting point of the resin (A) for more than 1 second and less than 10 minutes. The cooling step is to lower the temperature t of the molten mixture after maintaining it in the temperature range. 混合物 The step of cooling to a temperature below the crystallization temperature of the resin (A). Hereinafter, the holding step and the cooling step in the production method of the first embodiment are referred to as a holding step (ST2-1) and a cooling step (ST2-2), respectively.
[0124] In the fixing step (ST2), by sequentially performing the above-mentioned holding step (ST2-1) and cooling step (ST2-2), the particulate resin (A) in the polymer / polymer emulsion of the resin (A) and the resin (B) can be efficiently fixed in the form of a sphere with high sphericity and smooth surface. In the holding step (ST2-1), the temperature t of the molten mixture of the resin (A) and the resin (B) is raised to t 混合物 During the period of being maintained in the above temperature range for 1 second or more and 10 minutes or less, the temperature t of the above molten mixture can be lowered to 混合物 In the cooling step (ST2-2), the temperature of the molten mixture is kept constant, or the temperature may be increased or decreased. 混合物 The temperature drop rate and cooling time are set so as to lower the temperature to below the crystallization temperature of the resin (A).
[0125] In the holding step (ST2-1), the temperature of the molten mixture is 混合物 The holding time maintained in the above-mentioned temperature range is preferably more than 1 second and less than 10 minutes. The reason is that when the upper limit of the holding time is less than 10 minutes, it is easy to make the proportion of concave voids on the particle surface of the resin (A) after being fixed in the particle form sufficiently small, and polyamide particles (P1) with high sphericity and smooth surface can be efficiently produced. As the upper limit of the holding time, it is more preferably less than 5 minutes, further preferably less than 3 minutes, and particularly preferably less than 1 minute. In addition, the lower limit of the holding time is determined according to the temperature t used to melt the above-mentioned mixture. 混合物 In the case of operation of the device, the temperature is maintained within the above-mentioned temperature range for more than 1 second.
[0126] [Recycling process]
[0127] The manufacturing method of the first embodiment includes a recovery step as described above. The recovery step is a step of washing the molten mixture of the resin (A) and the resin (B) that form the polymer / polymer emulsion fixed in the above-mentioned fixing step (ST2) with a washing solution that is a non-solvent for the resin (A), thereby washing and removing the resin (B) from the molten mixture and recovering the polyamide microparticles (P1) made of the resin (A). Hereinafter, the recovery step in the manufacturing method of the first embodiment is referred to as a recovery step (ST3).
[0128] The cleaning solution used in the recovery step (ST3) is not particularly limited as long as it is a non-solvent for the resin (A) as described above and is a solvent capable of dissolving and removing the resin (B). Examples of such cleaning solutions include alcohols such as methanol, ethanol, and isopropanol, water-soluble ketones such as acetone, and water. From the perspective of economics during production and environmental friendliness, water is most preferably used as the cleaning solution.
[0129] As the cleaning method in the recovery process (ST3), as long as the resin (B) can be cleaned and removed from the fixed above-mentioned molten mixture, there is no particular limitation, and the method of making the above-mentioned molten mixture contact with the cleaning solution so that the resin (B) can be dissolved or removed from the above-mentioned molten mixture. For example, as the cleaning method, a cleaning method such as re-slurrying and cleaning while causing shear force or stirring force to act on the above-mentioned molten mixture can usually be used. In addition, in the recovery process (ST3), the above-mentioned molten mixture can also be heated appropriately. The concentration of the polyamide microparticles contained in the cleaning solution when cleaning the above-mentioned molten mixture is not particularly limited, and can be exemplified as 0.01 weight % or more and 50.00 weight % or less. From the viewpoint that the recovery efficiency of the resin particles in the cleaning operation becomes higher, the lower limit of the concentration of the polyamide microparticles is more preferably 0.05 weight % or more, further preferably 0.10 weight % or more, particularly preferably 0.50 weight % or more, and particularly preferably 1.00 weight % or more. From the viewpoint of efficiently removing the resin (B) from the molten mixture by one washing, the upper limit of the concentration of the polyamide fine particles is more preferably 40.00 wt % or less, and further preferably 30.00 wt % or less.
[0130] There is no particular restriction on the recovery method of the polyamide microparticles (P1) in the recovery step (ST3), and methods such as decompression, pressure filtration, decantation, centrifugation, and spray drying can be appropriately selected. In addition, the recovered polyamide microparticles (P1) can also be dried as needed. The drying treatment is preferably carried out below the melting point of the polyamide microparticles (P1), and can also be carried out while reducing pressure. There is no particular restriction on the drying method of the recovered polyamide microparticles (P1), and methods such as air drying, hot air drying, heating drying, reduced pressure drying, and freeze drying can be appropriately selected.
[0131] As described above, in the first embodiment of the present invention, polyamide particles (P1) are formed, which have a sphericity of 96 or more and are made of a polymer or copolymer having a repeating structural unit represented by the above chemical formula (1) as a main component. Therefore, the polyamide particles (P1) are marine biodegradable and have excellent sphericity and surface smoothness, thereby being able to be polyamide particles with small average deviations of the coefficient of kinetic friction when the particles are first rubbed against each other and average deviations of the coefficient of kinetic friction after the particles are continuously rubbed against each other over time. That is, the polyamide particles (P1) are marine biodegradable particles with excellent sliding properties when rubbed against each other.
[0132] Furthermore, by setting the standard deviation of the sphericity of the polyamide fine particles (P1) to 2.00 or less, the fluctuation of the sphericity of the polyamide fine particles (P1) can be suppressed, thereby promoting the reduction of the average deviation of the above-mentioned dynamic friction coefficients, thereby contributing to improving the sliding properties of the polyamide fine particles (P1) when they rub against each other.
[0133] In addition, by making the impurity content of the polyamide microparticles (P1) less than 0.50 weight %, or by making the temporal stability index of the polyamide microparticles (P1) greater than 0.60, it is possible to promote the reduction of the average deviation of the dynamic friction coefficient after the polyamide microparticles (P1) are rubbed against each other over time. As a result, it is possible to further improve the sliding properties of the polyamide microparticles (P1) after the temporal mutual friction, and as a result, the excellent sliding properties and good touch comfort of the polyamide microparticles (P1) can be maintained for a longer period of time. In addition, by making the polyamide microparticles (P1) satisfy both the impurity content of less than 0.50 weight % and the temporal stability index of more than 0.60, it is possible to further promote the reduction of the average deviation of the dynamic friction coefficient, and thus the above-mentioned sliding properties of the polyamide microparticles (P1) can be further improved. As a result, the excellent sliding properties and good touch comfort of the polyamide microparticles (P1) can be maintained for a longer period of time.
[0134] In addition, according to the method for producing polyamide microparticles according to the first embodiment of the present invention, polyamide microparticles (P1) having the above-mentioned excellent properties can be produced. In particular, by controlling the temperature of the resin (A) and the resin (B) when forming the polymer / polymer emulsion, and the temperature of the molten mixture of the resin (A) and the resin (B) when the molten mixture is fixed, the polyamide microparticles (P1) can be produced efficiently.
[0135] <Implementation Method 2>
[0136] (Polyamide microparticles)
[0137] The polyamide microparticles according to the second embodiment of the present invention are spherical polyamide microparticles with porous surfaces, characterized in that the ratio r of the voids on the particle surface is proportional to the BET specific surface area A. BET The ratio (r / A BET ) is 6.0 or more and 100.0 or less, and is made of a polymer or copolymer having as a main component a repeating structural unit represented by the following chemical formula (1). Therefore, the polyamide microparticles according to the second embodiment of the present invention have the following characteristics: they are marine biodegradable, and the average deviation of the dynamic friction coefficient immediately after the measurement and the average deviation of the dynamic friction coefficient after the passage of time are small, and in addition, they have excellent lipophilicity.
[0138]
[0139] (In the chemical formula (1), x is an integer of 2 or more and 3 or less.)
[0140] The structure and morphology of the polyamide microparticles (hereinafter sometimes referred to as polyamide microparticles (P2)) constituting the second embodiment of the present invention are described below. The polyamide microparticles (P2) are microparticles made of a polymer or copolymer having the structural unit represented by the above-mentioned chemical formula (1) as a main repeating structural unit. It should be noted that the chemical formula (1) in the second embodiment of the present invention is the same as the chemical formula (1) in the above-mentioned embodiment 1. That is, when x in the chemical formula (1) is not 2 or 3, the polyamide microparticles (P2) do not have sufficient marine biodegradability. From the perspective of the excellent operability of the polyamide microparticles (P2), the x is preferably 3. In addition, the polyamide microparticles (P2) may also contain a cross-linked structure or a branched structure within the range that does not impair the effect of the invention involved in the second embodiment.
[0141] The ratio of voids in the polyamide microparticles (P2) to the particle surface r and the BET specific surface area A BET The ratio (r / A BET) is 6.0 or more and 100.0 or less. The above-mentioned voids are concave voids on the porous surface of the polyamide microparticles (P2). The void ratio r is, for example, the ratio of the voids on the particle surface in a scanning electron microscope image obtained by photographing the polyamide microparticles (P2) from any direction to the surface area of the particle surface. BET specific surface area A BET is the specific surface area of the microparticles (polyamide microparticles (P2) in Embodiment 2) measured by the BET method. BET ) is less than 6.0, the affinity of the polyamide microparticles (P2) to the oil is reduced, for example, the dispersion stability of the polyamide microparticles (P2) in linseed oil is reduced. Therefore, when the polyamide microparticles (P2) are added to products such as paints and cosmetics, the dispersibility of the polyamide microparticles (P2) is reduced, resulting in a reduction in performance due to aggregation and sedimentation of the polyamide microparticles (P2), thereby impairing the feel of the product. In addition, the ratio (r / A) of the polyamide microparticles (P2) is preferably less than 6.0. BET ) is larger, the larger the BET specific surface area A BET Compared with other particles with the same value, the marine biodegradability of the polyamide particles (P2) tends to be higher. From the perspective of the lipophilicity and marine biodegradability of the polyamide particles (P2), the ratio (r / A BET ) is 6.0 or more, preferably 8.0 or more, more preferably 10.0 or more, and further preferably 12.0 or more. BET ) is greater than 100.0, the production of polyamide microparticles (P2) is basically difficult. BET ) has an upper limit of 100.0 or less.
[0142] BET specific surface area A of polyamide microparticles (P2) BET Preferably 0.8m 2 / g or more and 5.0m 2 The surface smoothness of the polyamide microparticles (P2) can be determined by the BET specific surface area A based on gas adsorption. BET The polyamide fine particles (P2) do not have a hollow structure, and the smoother the surface of the polyamide fine particles (P2), the greater the BET specific surface area A. BET The value becomes smaller. BET specific surface area A BET The smaller the value of is, the less deterioration of the touch comfort caused by the aggregation and entanglement of the polyamide fine particles (P2) will occur when the polyamide fine particles (P2) are continuously rubbed, and the smaller the average deviation of the dynamic friction coefficient after a period of time. BET The smaller the value, the better. From the perspective of the comfort of touch when the polyamide fine particles (P2) are continuously rubbed, the BET specific surface area A BET The upper limit value is preferably 5.0 m2 / g or less, more preferably 4.0m 2 / g or less, more preferably 3.0m 2 / g or less, and more preferably 2.0m 2 / g or less, particularly preferably 1.0 m 2 / g or less. In addition, if the BET specific surface area A BET 0.8m 2 / g or more, the marine biodegradability of the polyamide fine particles (P2) tends to be improved. BET The lower limit is preferably 0.8m 2 / g or more, more preferably 0.9m 2 / g or more. It should be noted that the BET specific surface area A of the polyamide microparticles (P2) is BET The measurement can be performed in the same manner as in the polyamide fine particles (P1) according to the first embodiment described above.
[0143] The ratio r of voids in the polyamide microparticles (P2) is the ratio of voids in the particle surface in a scanning electron microscope image obtained by photographing the particles from any direction, for example, and is preferably 5.0% or more and 80.0% or less. When the ratio r of voids is 5.0% or more, the biodegradability of the polyamide microparticles (P2) in the ocean is slightly improved. From the viewpoint of marine biodegradability, the lower limit of the ratio r of voids is preferably 5.0% or more, more preferably 10.0% or more, further preferably 20.0% or more, and particularly preferably 30.0% or more. In addition, if the ratio r of voids becomes too high, the particle shape of the polyamide microparticles (P2) cannot be maintained, and there is a tendency to significantly damage the particle characteristics of the polyamide microparticles (P2). Therefore, in order to present the particle characteristics of the polyamide microparticles (P2), the upper limit of the ratio r of voids is preferably 80.0% or less, more preferably 75.0% or less, and further preferably 70.0% or less.
[0144] The void ratio r can be obtained by randomly observing the surface irregularities of 50 particles from photographs of particles taken at 2,000 to 5,000 times using a scanning electron microscope, calculating the ratio of the concave area (i.e., the void area) of one particle to the surface area, and finding the average value thereof.
[0145] The sphericity of polyamide particles (P2) is preferably 90 or more. When the sphericity of polyamide particles (P2) is 90 or more, there is a tendency that the average deviation of the dynamic friction coefficient of polyamide particles (P2) becomes smaller, and the touch comfort when touching polyamide particles (P2) is improved. In addition, when polyamide particles (P2) are continuously rubbed, polyamide particles (P2) are not easy to agglomerate and entangle with each other, thus, the average deviation of the dynamic friction coefficient after time has also tended to become smaller, and the touch feeling when polyamide particles (P2) are continuously used is improved. Therefore, even when polyamide particles (P2) are used for cosmetics and coatings, a smooth touch can be given. From these viewpoints, as the lower limit of the sphericity of polyamide particles (P2), it is preferably 90 or more, more preferably 92 or more, further preferably 96 or more, especially preferably 97 or more, further preferably 98 or more, and particularly preferably 100. In addition, the upper limit of the sphericity of polyamide particles (P2) is 100 in theory.
[0146] The standard deviation of the sphericity of polyamide particles (P2) is preferably less than 2.00. If the standard deviation of the sphericity is less than 2.00, when polyamide particles (P2) are continuously rubbed, it is not easy to cause the deterioration of the touch comfort caused by agglomeration and entanglement, and the average deviation of the dynamic friction coefficient after the time elapses decreases. Thus, even when polyamide particles (P2) are used for the purposes of cosmetics and coatings, it is possible to give a smooth sense of touch, so it is preferred. The standard deviation of the sphericity of polyamide particles (P2) is more preferably less than 1.75, further preferably less than 1.50, particularly preferably less than 1.30, and particularly preferably less than 1.10. In addition, in polyamide particles (P2), the lower limit of the standard deviation of sphericity is theoretically 0.
[0147] The sphericity of the polyamide fine particles (P2) and the standard deviation of the sphericity can be calculated based on the mathematical formula (1) and the mathematical formula (2), respectively, similarly to the polyamide fine particles (P1) in the first embodiment.
[0148] The volume average particle size of the polyamide microparticles (P2) is preferably within the range of 0.1 μm or more and 100.0 μm or less. If the volume average particle size of the polyamide microparticles (P2) is 100.0 μm or less, the touch when touching the polyamide microparticles (P2) is excellent, and the average deviation of the coefficient of kinetic friction after the initial measurement is reduced, so it is preferred. As the upper limit of the volume average particle size of the polyamide microparticles (P2), it is more preferably 50.0 μm or less, further preferably 30.0 μm or less, particularly preferably 15.0 μm or less, more preferably 13.0 μm or less, and particularly preferably 10.0 μm or less. In addition, if the volume average particle size of the polyamide microparticles (P2) is 0.1 μm or more, it is not easy to produce agglomeration of the polyamide microparticles (P2) with each other, the reduction of the touch caused by agglomeration can be suppressed, and the average deviation of the coefficient of kinetic friction after the initial measurement and after the passage of time is reduced, so it is preferred. The lower limit of the volume average particle size of the polyamide fine particles (P2) is more preferably 0.3 μm or more, further preferably 0.5 μm or more, and particularly preferably 1.0 μm or more.
[0149] The particle size distribution index representing the particle size distribution of the polyamide microparticles (P2) is preferably 3.0 or less. If the particle size distribution index is 3.0 or less, the fluidity is excellent and the sliding property is improved in the applications such as coatings and cosmetics using the polyamide microparticles (P2). The particle size distribution index of the polyamide microparticles (P2) is more preferably 2.0 or less, further preferably 1.5 or less, particularly preferably 1.3 or less, and particularly preferably 1.2 or less. In addition, the lower limit of the particle size distribution index of the polyamide microparticles (P2) is theoretically 1.0.
[0150] It should be noted that, similarly to the polyamide microparticles (P1) of the first embodiment, the volume average particle size and the number average particle size of the polyamide microparticles (P2) refer to the values measured using a laser diffraction / scattering particle size distribution meter. In addition, the particle size distribution index of the polyamide microparticles (P2) can be calculated based on mathematical formula (3) similarly to the polyamide microparticles (P1) of the first embodiment.
[0151] The weight average molecular weight of the polyamide microparticles (P2) is preferably 2,000 or more and 2,000,000 or less. If the weight average molecular weight is 2,000 or more, when the polyamide microparticles (P2) are continuously rubbed, it is not easy to cause the deterioration of the touch comfort caused by the agglomeration and entanglement of the polyamide microparticles (P2), and the average deviation of the dynamic friction coefficient after the time has passed becomes smaller, so it is preferred. As the lower limit of the weight average molecular weight of the polyamide microparticles (P2), it is more preferably 3,000 or more, further preferably 4,000 or more, and particularly preferably 5,000 or more. If the weight average molecular weight of the polyamide microparticles (P2) is 2,000,000 or less, the average deviation of the dynamic friction coefficient after the measurement is just started becomes smaller, and the touch when the polyamide microparticles (P2) are rubbed against each other is excellent, so it is preferred. The upper limit of the weight average molecular weight of the polyamide fine particles (P2) is more preferably 1,000,000 or less, further preferably 500,000 or less, particularly preferably 100,000 or less, particularly preferably 50,000 or less, and even more preferably less than 30,000. The weight average molecular weight of the polyamide fine particles (P2) can be measured in the same manner as the polyamide fine particles (P1) of the first embodiment described above.
[0152] The weight of the entire polyamide microparticle (P2) is set to 100.00 weight %, and the impurity content of the polyamide microparticle (P2) is preferably 0.50 weight % or less. The impurities contained in the polyamide microparticle (P2) are components other than the resin (A) contained in the polyamide microparticle (P2), and the same components as the polyamide microparticle (P1) of the above-mentioned embodiment 1 can be exemplified. If the impurity content of the polyamide microparticle (P2) is 0.50 weight % or less, when the polyamide microparticle (P2) is continuously rubbed, it is not easy to cause the deterioration of the touch comfort caused by the agglomeration and entanglement of the polyamide microparticle (P2), and the average deviation of the dynamic friction coefficient after the time is small. Therefore, even when the polyamide microparticle (P2) is used for cosmetics and coatings, it is possible to give a smooth touch, so it is preferred. The impurity content of the polyamide microparticle (P2) is more preferably 0.30 weight % or less, and particularly preferably 0.10 weight % or less. In addition, the lower limit of the impurity content of the polyamide microparticle (P2) is theoretically 0.00 weight %. In addition, the impurity content of the polyamide fine particles (P2) can be obtained in the same manner as the polyamide fine particles (P1) of the first embodiment described above.
[0153] The temporal stability index of polyamide particles (P2) is an index defined in the same manner as in the above-mentioned embodiment 1, preferably 0.60 or more. The greater the temporal stability index of polyamide particles (P2), the better the touch can be maintained even if polyamide particles (P2) are continuously rubbed for a long time. For example, even when polyamide particles (P2) are used in cosmetic applications, the excellent touch of polyamide particles (P2) can be maintained for a long time. Especially when the temporal stability index is 0.60 or more, when polyamide particles (P2) are continuously rubbed, the deterioration of the touch comfort caused by the agglomeration and entanglement of polyamide particles (P2) is not easy to occur, and the average deviation of the dynamic friction coefficient after the time is reduced, so it is preferred. As the lower limit of the temporal stability index of polyamide particles (P2), it is more preferably 0.70 or more, and more preferably 0.80 or more. It should be noted that the temporal stability index of the polyamide fine particles (P2) can be calculated by the above-mentioned mathematical formula (4) in the same manner as the polyamide fine particles (P1) of the above-mentioned embodiment 1. At this time, in the above-mentioned mathematical formula (4), s is the standard deviation of the sphericity of the polyamide fine particles (P2), and the impurity content is the impurity content of the polyamide fine particles (P2).
[0154] In addition, the polyamide microparticles (P2) have the same marine biodegradability as that of the polyamide microparticles (P1) of the first embodiment. From the viewpoint of exhibiting good marine biodegradability of the polyamide microparticles (P2), the lower limit of the marine biodegradability of the polyamide microparticles (P2) is preferably 15% or more, more preferably 20% or more, and further preferably 30% or more. In addition, if the marine biodegradability is too high, the period during which the polyamide microparticles (P2) are used as a product (the product life of the polyamide microparticles (P2)) can be shortened. Therefore, the upper limit of the marine biodegradability of the polyamide microparticles (P2) is preferably 90% or less, and more preferably 80% or less.
[0155] (Method for producing polyamide microparticles)
[0156] Next, the method for producing polyamide microparticles according to the second embodiment of the present invention will be described in detail. The polyamide microparticles (P2) described above can be produced by the production method according to the second embodiment of the present invention.
[0157] In detail, the method for producing polyamide microparticles according to the second embodiment of the present invention (hereinafter, sometimes referred to as the method for producing polyamide microparticles according to the second embodiment) is a method for producing polyamide microparticles (P2) using resin (A) and resin (B) as raw materials, wherein the resin (A) is a polymer or copolymer having a repeating structural unit represented by the above-mentioned chemical formula (1) as a main component, and the resin (B) is an emulsion-forming resin that can form an emulsion with the resin (A) in a molten state. The method for producing polyamide microparticles according to the second embodiment includes an emulsion-forming step, a fixation step, and a recovery step. The emulsion-forming step is a step of melt-mixing the resin (A) and the resin (B) at a temperature (melting temperature) above their respective melting points to form an emulsion (polymer / polymer emulsion) in which particles of the resin (A) are dispersed in the resin (B). The fixation step is a step of cooling the molten mixture of the resin (A) and the resin (B) forming the emulsion to below the crystallization temperature of the resin (A) to fix the emulsion. The recovery step is a step of washing away the resin (B) in the fixed molten mixture using a washing solution that is a non-solvent for the resin (A) to recover the polyamide microparticles (P2) made of the resin (A). In addition, in the production method of the second embodiment, the melt viscosity ratio of the resin (A) to the resin (B) at 270° C. is 4.3 or more and 125.0 or less.
[0158] [Resin (A) and Resin (B)]
[0159] In the production method of the second embodiment, the resin (A) and the resin (B) as raw materials of the polyamide fine particles (P2) are respectively the same as the resin (A) and the resin (B) in the production method of the first embodiment described above.
[0160] For example, the resin (A) of the second embodiment is a polymer or copolymer having the repeating structural unit represented by the above chemical formula (1) as the main component, and may also contain a cross-linked structure or a branched structure within the range that does not impair the effect of the invention involved in the second embodiment. In addition, the melt viscosity of the resin (A) of the second embodiment at 270° C., the method for deriving the melt viscosity, the polymerization method, the copolymerization components, etc. are also the same as those of the first embodiment described above.
[0161] Similar to the above-mentioned embodiment 1, the resin (B) of embodiment 2 is an emulsion-forming resin that can form a polymer / polymer emulsion with the above-mentioned resin (A) in a molten state. As specific examples of the resin (B), the same resins as those in the above-mentioned embodiment 1 can be cited. In particular, as the most preferred specific example of the resin (B), polyethylene glycol can be cited, similar to the above-mentioned embodiment 1. In addition, the melt viscosity of the resin (B) at 270°C and the method for deriving it are also the same as those in the above-mentioned embodiment 1. For example, the melt viscosity is preferably greater than 0.40 Pa·s and less than 5.00 Pa·s.
[0162] In addition, in the manufacturing method of embodiment 2, the melt viscosity ratio of resin (A) to resin (B) at 270°C is 4.3 or more and 125.0 or less. In this manufacturing method, resin (A) and resin (B) form a polymer / polymer emulsion in a molten state, which enables the formation of polyamide particles (P2) with a porous surface and moderately high sphericity and little fluctuation of sphericity. Therefore, this is necessary from the perspective of making polyamide particles (P2) with marine biodegradability, in which the average deviation of the dynamic friction coefficient when the particles rub against each other is small and the average deviation of the dynamic friction coefficient after time is also small. Although the principle cannot be explained in detail, only when the resin (A) and the resin (B) whose melt viscosity ratio satisfies the condition of 4.3 or more and 125.0 or less are melt-mixed, the interfacial tension and melt viscosity of these resins (A) and resin (B) are maintained within a suitable range, and as a result, the characteristics of the polyamide particles (P2) can be obtained.
[0163] When the melt viscosity ratio of resin (A) to resin (B) at 270°C is less than 4.3, the particle size of the emulsion of resin (A) in resin (B) becomes too large in the molten state of resin (A) and resin (B), so that a polymer / polymer emulsion of resin (A) and resin (B) cannot be formed. From the viewpoint of improving the smoothness of the polyamide microparticles (P2) when touched, reducing the foreign body feeling, and reducing the average deviation of the dynamic friction coefficient immediately after the measurement, the melt viscosity ratio is preferably 10.0 or more, more preferably 15.0 or more, and even more preferably 20.0 or more.
[0164] On the other hand, when the melt viscosity ratio of resin (A) to resin (B) at 270°C is greater than 125.0, the particle size of the emulsion of resin (A) formed in resin (B) becomes excessively small, and the stability of the emulsion of resin (A) and resin (B) is lost, so that polyamide microparticles (P2) cannot be obtained. From the viewpoint of improving the touch comfort of polyamide microparticles (P2) when rubbing continuously and reducing the average deviation of the dynamic friction coefficient after a period of time, the melt viscosity ratio is preferably 100.0 or less, more preferably 75.0 or less, further preferably 50.0 or less, and particularly preferably 40.0 or less. It should be noted that the melt viscosity ratio in Embodiment 2 can be calculated based on the same mathematical formula (5) as in Embodiment 1 described above.
[0165] [Emulsion Formation Step]
[0166] The manufacturing method of the second embodiment includes an emulsion forming step as described above. Hereinafter, the emulsion forming step in the manufacturing method of the second embodiment is referred to as an emulsion forming step (ST11). The emulsion forming step (ST11) is the same as the emulsion forming step (ST1) in the first embodiment described above, and is a step of melt-mixing the resin (A) and the resin (B) at a melting temperature above their respective melting points to form a polymer / polymer emulsion of the resin (A) and the resin (B).
[0167] For example, the melting temperature in the emulsion forming step (ST11) is the temperature when the resin (A) and the resin (B) are melt-mixed, and can be selected according to the type of resin (A) in the same manner as the emulsion forming step (ST1) of the above-mentioned embodiment 1. From the viewpoint of producing polyamide microparticles (P2) having a porous surface and a higher sphericity and a small standard deviation of sphericity, the above-mentioned melting temperature is preferably a temperature of the melting point of the resin (A) + 5°C or more. On the other hand, from the viewpoint of being able to suppress the decomposition of the resin (A) in a state of being melt-mixed with the resin (B) and being able to form a stable polymer / polymer emulsion of the resin (A) and the resin (B), and further improving the sphericity of the obtained polyamide microparticles (P2), the upper limit of the above-mentioned melting temperature is preferably below 280°C. From the viewpoint of further improving the sphericity, the upper limit of the above-mentioned melting temperature is more preferably below 270°C.
[0168] In addition, in the emulsion forming step (ST11), from the viewpoint that the sphericity of the obtained polyamide microparticles (P2) is high and the standard deviation of the sphericity is small, it is preferred to include a heating step of heating the resin (A) and the resin (B) as raw materials from room temperature to the above-mentioned melting temperature, similarly to the emulsion forming step (ST1) of the above-mentioned embodiment 1.
[0169] In addition, in the emulsion forming step (ST11), fine particles can be produced even if the molten mixture of the resin (A) and the resin (B) is not stirred, but in order to uniformly control the volume average particle size and particle size distribution of the obtained polyamide particles (P2), the molten mixture may be stirred. The stirring device and stirring speed at this time are the same as those in the emulsion forming step (ST1) of the above-mentioned embodiment 1.
[0170] It should be noted that, in the emulsion forming step (ST11), the melt mixing time of the resin (A) and the resin (B), and the method of deriving the melting points of the resin (A) and the resin (B) are the same as those in the emulsion forming step (ST1) of the above-mentioned embodiment 1. In addition, in the emulsion forming step (ST11), the melt mixing ratio of the resin (A) and the resin (B), and the addition of additives when the resin (A) and the resin (B) are melt mixed are also the same as those in the emulsion forming step (ST1) of the above-mentioned embodiment 1.
[0171] [Immobilization process]
[0172] The manufacturing method of the second embodiment includes a fixing step as described above. The fixing step is a step of cooling the molten mixture of the resin (A) and the resin (B) obtained in the emulsion forming step (ST11) to form a polymer / polymer emulsion to a temperature below the crystallization temperature of the resin (A), thereby fixing the polymer / polymer emulsion. Hereinafter, the fixing step in the manufacturing method of the second embodiment is referred to as a fixing step (ST12).
[0173] The fixing step (ST12) preferably includes a holding step and a cooling step as shown below. The holding step is to lower the temperature t of the molten mixture of the resin (A) and the resin (B) to 混合物 The cooling step is to lower the temperature of the molten mixture after being kept in the above temperature range to a temperature range higher than the crystallization temperature of the resin (A) and lower than the melting point of the resin (A). 混合物 The step of cooling to a temperature below the crystallization temperature of the resin (A). Hereinafter, the holding step and the cooling step in the production method of the second embodiment are referred to as a holding step (ST12-1) and a cooling step (ST12-2), respectively.
[0174] In the fixation process (ST12), by sequentially performing the above-mentioned holding process (ST12-1) and cooling process (ST12-2), the particulate resin (A) in the polymer / polymer emulsion of resin (A) and resin (B) can be efficiently fixed in a spherical shape having a porous surface.
[0175] In the holding step (ST12-1) in the fixing step (ST12), it is preferred to lower the temperature t of the molten mixture of the resin (A) and the resin (B) to t 混合物 The temperature is maintained in the above temperature range for more than 30 minutes and less than 10 hours. 混合物 During the holding step (ST12-1), the temperature t of the molten mixture may be kept at 混合物 Keep it constant, or you can heat it up or cool it down.
[0176] In the holding step (ST12-1), the temperature t of the molten mixture in the above temperature range is 混合物 When the holding time is 30 minutes or more, the crystallization of the resin (A) is carried out while maintaining the shape of the emulsion formed in the emulsion forming step (ST11), thereby producing spherical polyamide particles (P2) whose surface is made porous and formed into a spherical shape. 混合物 The lower limit of the holding time is preferably 30 minutes or more. From the viewpoint of increasing the ratio r of the voids on the surface of the polyamide microparticles (P2), the temperature t 混合物 The lower limit of the holding time is more preferably 45 minutes or more, and further preferably 60 minutes or more. In addition, the temperature t of the molten mixture in the above temperature range is 混合物 When the holding time is 10 hours or less, the decomposition of the crystallized resin (A) can be suppressed, thereby improving the sphericity of the polyamide microparticles (P2) and reducing the standard deviation of the sphericity. 混合物 The upper limit of the retention time is preferably 10 hours or less, more preferably 8 hours or less, further preferably 5 hours or less, particularly preferably 3 hours or less, and particularly preferably 2 hours or less.
[0177] It should be noted that the temperature of the molten mixture in the above temperature range is 混合物 When the holding time is more than 10 hours or less than 30 minutes, the polyamide fine particles (P1) with smooth surface and high spherical shape in the first embodiment and the polyamide fine particles (P2) with porous surface and spherical shape in the second embodiment are mixed together, and as a result, the properties of the polyamide fine particles (P1) and the polyamide fine particles (P2) are hindered. 混合物 A holding time of more than 10 hours or less than 30 minutes is not preferred.
[0178] In the cooling step (ST12-2) in the fixing step (ST12), the temperature t of the molten mixture is adjusted to a temperature t that allows the molten mixture to be kept in the temperature range in the keeping step (ST12-1).混合物 The temperature drop rate and cooling time are set so as to lower the temperature to below the crystallization temperature of the resin (A).
[0179] As a method for cooling the molten mixture of resin (A) and resin (B) in the fixing step (ST12), any method can be used as long as the effects of the invention related to Embodiment 2 are not impaired. For example, as the cooling method, the same specific example as the fixing step (ST2) in Embodiment 1 mentioned above can be cited.
[0180] [Recycling process]
[0181] The manufacturing method of the second embodiment includes a recovery step as described above. The recovery step is a step of washing the molten mixture of the resin (A) and the resin (B) that forms the polymer / polymer emulsion fixed in the above-mentioned fixing step (ST12) with a washing solution that is a non-solvent for the resin (A), thereby washing and removing the resin (B) from the molten mixture and recovering the polyamide microparticles (P2) made of the resin (A). Hereinafter, the recovery step in the manufacturing method of the second embodiment is referred to as a recovery step (ST13).
[0182] In addition, the cleaning solution, the cleaning method, and the method for recovering the polyamide fine particles (P2) in the recovery step (ST13) are the same as those in the recovery step (ST3) of the first embodiment described above.
[0183] As described above, in the second embodiment of the present invention, the ratio r of the voids on the particle surface and the BET specific surface area A BET The ratio (r / A BET ) is 6.0 or more and 100.0 or less, and is made of a polymer or copolymer having a repeating structural unit represented by the above chemical formula (1) as a main component. Therefore, the polyamide microparticles (P2) can become a polyamide microparticle with a BET specific surface area A BET Polyamide fine particles having excellent marine biodegradability and lipophilicity, and having both a smaller average deviation of the kinetic friction coefficient when the fine particles are initially rubbed against each other and a smaller average deviation of the kinetic friction coefficient after the fine particles are continuously rubbed against each other over time than other equivalent fine particles. That is, the polyamide fine particles (P2) are fine particles having excellent marine biodegradability and lipophilicity, and excellent sliding properties when rubbed against each other.
[0184] Furthermore, by setting the standard deviation of the sphericity of the polyamide microparticles (P2) to 2.00 or less, the fluctuation of the sphericity of the polyamide microparticles (P2) can be suppressed, thereby promoting the reduction of the average deviation of the above-mentioned coefficients of kinetic friction, thereby contributing to improving the sliding properties of the polyamide microparticles (P2) when they rub against each other.
[0185] In addition, by making the BET specific surface area A of the polyamide fine particles (P2) BET 0.8m 2 / g or more and 5.0m 2 / g or less, the average variation of the above-mentioned dynamic friction coefficients can be reduced, thereby contributing to improving the sliding property when the polyamide fine particles (P2) rub against each other, and further improving the marine biodegradability.
[0186] In addition, according to the method for producing polyamide microparticles according to the second embodiment of the present invention, polyamide microparticles (P2) having the above-mentioned excellent properties can be produced. In particular, by controlling the temperature of the molten mixture (polymer / polymer emulsion) of the resin (A) and the resin (B) as raw materials when the molten mixture is fixed, the polyamide microparticles (P1) according to the first embodiment and the polyamide microparticles (P2) according to the second embodiment can be produced separately, thereby efficiently producing the target polyamide microparticles (P2).
[0187] <Purpose>
[0188] The polyamide particles (P1) involved in embodiment 1 of the present invention and the polyamide particles (P2) involved in embodiment 2 have marine biodegradability, excellent sphericity, and the average deviation of the dynamic friction coefficient after the initial measurement and after the passage of time is small. The average deviation of the dynamic friction coefficient after the initial measurement is a numerical value representing the touch of the polyamide particles just after touching. The smaller the average deviation of the dynamic friction coefficient after the initial measurement, the less foreign body feeling and roughness when the polyamide particles are rubbed against each other with fingers, and the excellent touch when touched. Therefore, the polyamide particles (P1) and polyamide particles (P2) with a small average deviation of the dynamic friction coefficient after the initial measurement can be suitable for use in, for example, cosmetics. The average deviation of the dynamic friction coefficient after the passage of time is a numerical value indicating the presence or absence of deterioration of touch comfort caused by agglomeration and entanglement when the polyamide particles are continuously rubbed. The smaller the average deviation of the dynamic friction coefficient after the passage of time, the more difficult it is to deteriorate the touch comfort caused by agglomeration and entanglement of polyamide particles. Therefore, even when the polyamide fine particles (P1) and the polyamide fine particles (P2) are suitably used for applications such as cosmetics and coatings, the smoothness of the product can be maintained for a long period of time, and an excellent touch can be imparted.
[0189] In addition, the polyamide microparticles (P1) according to the first embodiment of the present invention and the polyamide microparticles (P2) according to the second embodiment have high sphericity and small average deviations of the coefficient of kinetic friction immediately after measurement and after a certain period of time. Therefore, if they are added to cosmetics, in addition to obtaining smoothness during use, a soft focus effect (i.e., light is scattered in various directions by covering the unevenness of the skin, thereby making wrinkles less noticeable) can be obtained. In addition, the polyamide microparticles (P2) also have excellent lipophilicity. Therefore, when added to cosmetics, they have good affinity with oil agents and can further improve the touch.
[0190] As cosmetics, the cosmetics include foundations such as liquid foundation and powder foundation, concealer, sunscreen, base makeup, lipstick and lipstick base, talcum powder, white powder such as solid white powder and loose powder, solid powder eye shadow, wrinkle cream, and skin care lotion, etc., which are mainly used for external use on skin and hair for the purpose of makeup, and the dosage form is not limited. As the dosage form, it can be any dosage form of liquid preparations such as aqueous solution, emulsion, suspension, semi-solid preparations such as gel and cream, powder, granule and solid preparations. In addition, as the dosage form, emulsion dosage forms such as cream and emulsion, oily gel dosage forms such as lipstick, powder dosage forms such as foundation, and aerosol dosage forms such as hair setting agent can be cited.
[0191] In addition, the above-mentioned polyamide fine particles (P1) and polyamide fine particles (P2) can be used for purposes other than cosmetics, for example, in coatings used in buildings, automobiles, metal products, electrical appliances, etc., and in toners used in laser printers and copiers, etc., and other uses that utilize sphericity, and there is no limitation on the use.
[0192] The polyamide microparticles (P1) and polyamide microparticles (P1) can be manufactured respectively by the manufacturing methods of the above-mentioned embodiments 1 and 2. In particular, in the present invention, it is possible to easily manufacture polyamide microparticles having marine biodegradability and in which the average deviation of the dynamic friction coefficient when the microparticles rub against each other is small and the average deviation of the dynamic friction coefficient after the passage of time is also small, which has been difficult before.
[0193] Example
[0194] Hereinafter, the present invention will be described in more detail based on examples, but the present invention is not limited to these examples. Materials, evaluation items and evaluation methods used in examples and comparative examples are as follows.
[0195] [Sphericity, standard deviation of sphericity]
[0196] The sphericity and standard deviation of the sphericity of the polyamide microparticles were obtained by randomly observing 50 polyamide microparticles from photographs of the polyamide microparticles taken under the following conditions using a scanning electron microscope, and calculating the sphericity from the minor and major axes thereof using the following mathematical formulas (1) and (2). The sphericity values were rounded off and expressed as integers, for example, 99.5 or more was expressed as 100.
[0197] <Conditions>
[0198] ·Device: TM1000 miniscope made by Hitachi Hakusho Co., Ltd.
[0199] Shooting magnification: 2,000 to 5,000 times
[0200]
[0201] (T: sphericity (average), a i : The major diameter of each polyamide microparticle, b i : the short diameter of each polyamide microparticle, n: the number of measurements)
[0202]
[0203] (s: standard deviation of sphericity, T i : sphericity of each polyamide microparticle, T: sphericity (average), n: number of measurements)
[0204] In the examples and comparative examples, when deriving the sphericity and the standard deviation of the sphericity of the polyamide microparticles, the number of measurements n in the mathematical formula (1) and the mathematical formula (2) was set to 50.
[0205] [BET specific surface area]
[0206] About the BET specific surface area A of polyamide microparticles BET According to Japanese Industrial Standard (JIS standard) JIS R1626 (1996) "Determination of specific surface area by gas adsorption BET method", the krypton gas adsorption isotherm at liquid nitrogen temperature was measured under the following conditions and calculated by BET method.
[0207] <Conditions>
[0208] ·Device: BELSORP-max made by Japan Hura Corporation
[0209] Gas: Krypton
[0210] Sample volume: about 0.2g
[0211] Pretreatment: 80℃, decompression degassing for about 5 hours
[0212] [The ratio of voids r, ratio (r / A BET )]
[0213] The ratio r of voids on the surface of the polyamide microparticles was calculated based on 50 polyamide microparticles randomly selected from photographs of the polyamide microparticles taken under the following conditions using a scanning electron microscope. At this time, the surface of each polyamide microparticle was binarized using image analysis software, and the ratio of the concave area to the surface area of each polyamide microparticle was calculated, and the target ratio r of voids was obtained from the average value.
[0214] <Conditions>
[0215] ·Device: TM1000 miniscope manufactured by Hitachi Hakusho Co., Ltd.
[0216] Shooting magnification: 2,000 to 5,000 times
[0217] Image analysis software: Winroof
[0218] In addition, the void ratio r calculated as described above is divided by the BET specific surface area A BET The value of , thus calculating the void ratio r and BET specific surface area A BET The ratio (r / A BET ).
[0219] [Volume average particle size, particle size distribution index]
[0220] The volume average particle size and number average particle size of the polyamide microparticles were determined under the following conditions: The particle size distribution index was calculated from the following mathematical formula (3) using the values of the volume average particle size and number average particle size determined as described above.
[0221] <Conditions>
[0222] · Equipment: Laser diffraction / scattering particle size distribution analyzer (Microtrac MT3300EXII) manufactured by Nikkiso Co., Ltd.
[0223] Dispersion medium: water
[0224] Flow rate: 50%
[0225] Cleaning times: 3 times
[0226] Ultrasonic output power: 40W
[0227] Ultrasonic time: 180 seconds
[0228] Degassing times: 3 times
[0229] Particle size distribution index = volume average particle size / number average particle size ... mathematical formula (3)
[0230] [Melting point, crystallization temperature]
[0231] The melting point and crystallization temperature of the resin (A) as a raw material of the polyamide microparticles were measured under the following conditions, the top of the exothermic peak appearing in step (c) of the following temperature program was taken as the crystallization temperature, and the endothermic peak in step (e) of the following temperature program was taken as the melting point.
[0232] <Conditions>
[0233] · Apparatus: Differential scanning calorimeter (DSCQ20) manufactured by TA Instruments
[0234] Sample volume: 10 mg
[0235] Atmosphere: Nitrogen flow
[0236] Temperature program:
[0237] Step (a) The temperature is raised from 30°C to an endothermic peak showing the melting point of polyamide.
[0238] Step (b) Hold for 1 minute
[0239] Step (c) Cooling to 30°C
[0240] Step (d) Hold for 1 minute
[0241] Step (e) heating from 30°C to an endothermic peak showing the melting point of polyamide
[0242] Heating and cooling speed: 20℃ / min
[0243] [Melt viscosity, melt viscosity ratio]
[0244] The melt viscosities of the resin (A) and the resin (B) as the raw materials of the polyamide microparticles were determined by obtaining the values of the melt viscosities measured under the following conditions 5 minutes after the start of the measurement as the respective melt viscosities. In addition, the melt viscosity ratio of the resin (B) to the resin (A) was calculated by the following mathematical formula (5) using the obtained melt viscosities.
[0245] <Conditions>
[0246] ·Device: Physica MCR501 manufactured by Anton Paar
[0247] ·Measurement fixture: parallel plate (PP25, φ25mm)
[0248] ·Measurement position: 1.0mm
[0249] Frequency: 1Hz
[0250] Temperature condition: 270℃
[0251] Melt viscosity ratio = melt viscosity of resin (B) / melt viscosity of resin (A) ... Mathematical formula (5)
[0252] [Impurity content]
[0253] The impurity content of the polyamide microparticles was determined by measuring the organic and inorganic substances other than the resin (A) contained in the polyamide microparticles under the following conditions, and the total amount was obtained as the impurity content. In addition, when the impurity content was much lower than 0.1 wt % and could not be detected, it was recorded as undetectable.
[0254] The content of organic matter in the impurities of polyamide microparticles is calculated by 1 H-NMR was obtained under the following conditions.
[0255] <Conditions>
[0256] · Equipment: 500MHz nuclear magnetic resonance equipment manufactured by JEOL
[0257] Nuclide: 1 H
[0258] Sample concentration: about 1% by weight
[0259] Solvent: D 2 SO 4
[0260] Cumulative times: 256 times
[0261] The content of inorganic substances in the impurity content of the polyamide fine particles was determined from the weight of ash recovered by calcining about 5 g of the polyamide fine particles in an electric furnace under the following conditions and cooling the calcined polyamide fine particles.
[0262] <Conditions>
[0263] ·Device: TMF-5 made by Tomas Scientific Instruments Co., Ltd.
[0264] Ashing temperature: 550℃
[0265] Ashing time: 6 hours
[0266] [Weight average molecular weight]
[0267] The weight average molecular weight of the polyamide fine particles was determined by dissolving 0.5 g of the polyamide fine particles in 4 mL of HFIP (0.005 N sodium trifluoroacetate added), filtering the mixture with a 0.45 μm filter, and measuring the resulting solution under the following conditions.
[0268] <Conditions>
[0269] · Apparatus: Gel Permeation Chromatography (manufactured by Waters)
[0270] Detector: Differential refractometer Waters 410 (manufactured by Waters)
[0271] ·Column: Shodex GPC HFIP-806M (2 pieces) + HFIP-LG (manufactured by Shimadzu Corporation)
[0272] Flow rate: 0.5mL / min
[0273] Sample injection volume: 0.1mL
[0274] Temperature: 30℃
[0275] Molecular weight calibration: polymethyl methacrylate (PMMA)
[0276] [Time stability index]
[0277] The temporal stability index of polyamide microparticles is calculated by the following mathematical formula (4) using the above-mentioned standard deviation of sphericity and impurity content. When the impurity content is undetectable, the temporal stability index of polyamide microparticles is calculated by setting the impurity content in mathematical formula (4) to 0.0.
[0278] Temporal stability index = 1 / (s×(impurity content+1))…Mathematical formula (4)
[0279] (s: standard deviation of sphericity)
[0280] [Marine biodegradability]
[0281] The marine biodegradability of polyamide microparticles was evaluated by mixing 100 mg of polyamide microparticles into 100 g of soil and measuring BOD according to Japanese Industrial Standards (JIS) JIS K6955 (2006). When the polyamide microparticles showed 10% or more decomposition after 2 months from the start of the test, the polyamide microparticles were considered to be marine biodegradable.
[0282] [Kinematic friction coefficient when particles rub against each other]
[0283] As an index of the touch of polyamide fine particles, polyamide fine particles were applied to a sample table so as to be smooth, and the sample table was moved to measure under the following conditions. The average deviation of the dynamic friction coefficient at this time was determined from 10 measurements.
[0284] <Conditions>
[0285] · Device: KES-SE-STP Friction Tester manufactured by Katotech
[0286] Sample volume: 0.01g
[0287] Sample table area: 2cm×10cm
[0288] Sample stage moving speed: 1mm / min
[0289] The tactile feel of the polyamide microparticles immediately after being touched can be represented by the average deviation of the kinetic friction coefficient immediately after the above-mentioned measurement (hereinafter referred to as the average deviation of the kinetic friction coefficient immediately after the measurement). The smaller the average deviation of the kinetic friction coefficient immediately after the measurement, the smoother and better tactile feel with less foreign matter feeling and roughness when the polyamide microparticles are rubbed with fingers.
[0290] In addition, the presence or absence of deterioration of touch comfort due to agglomeration and entanglement of polyamide microparticles when the polyamide microparticles are continuously rubbed can be indicated by the average deviation of the dynamic friction coefficient 5 minutes after the start of the above-mentioned measurement (hereinafter referred to as the average deviation of the dynamic friction coefficient after 5 minutes). The smaller the average deviation of the dynamic friction coefficient after 5 minutes, the less deterioration of touch comfort due to agglomeration and entanglement of polyamide microparticles occurs, and even when used for cosmetics, coatings, etc., a smooth and excellent touch feeling can be given.
[0291] [Dispersion stability in linseed oil]
[0292] As an index of the lipophilicity of the polyamide microparticles, the dispersion stability in linseed oil was evaluated. In this evaluation, after the polyamide microparticles were dispersed in linseed oil, the permeability of the linseed oil just after the dispersion and the permeability of the linseed oil after one day of standing after the dispersion were measured under the following conditions, and the difference was calculated by the following mathematical formula (6).
[0293] <Conditions>
[0294] · Installation: TURBISCAN Lab manufactured by Sanyo Trading Co., Ltd.
[0295] Sample volume: 2g
[0296] Flaxseed oil: 18g
[0297] Sample bottle capacity: 20mL
[0298] ·Measurement position: 3mm from the bottom of the sample bottle
[0299] Dispersion stability in linseed oil = permeability immediately after dispersion - permeability after 1 day
[0300] …Mathematical formula (6)
[0301] The smaller the difference in the above transmittance of the polyamide microparticles, the better the lipophilicity. When the difference in the above transmittance is 20 or less, the lipophilicity can be said to be sufficiently high. If the lipophilicity is high, when the polyamide microparticles are added to the oil, the dispersed state can be stably maintained in the oil, and the characteristics of the polyamide microparticles can be exerted without being impaired.
[0302] <Reference Example 1>
[0303] In Reference Example 1, as an example of resin (A) (which is a raw material of polyamide microparticles), resin (A)-1 was synthesized. Specifically, in a 50°C oil bath, 2-pyrrolidone (127.7 g (1500 mmol)) and potassium tert-butoxide (3.37 g (30 mmol)) purified and water removed were added to a 500 mL flask and dissolved uniformly. 1-acetyl-2-caprolactam (3.46 g (30 mmol)) was added as an initiator, and after nitrogen substitution in the system, polymerization was performed for 4 hours to obtain a block. The obtained block was crushed, washed with ethanol, and vacuum dried at 80°C for 24 hours to obtain a 2-pyrrolidone polymer, resin (A)-1, having a melting point of 263°C, a crystallization temperature of 232°C, and a melt viscosity of 0.04 Pa·s.
[0304] <Reference Example 2>
[0305] In Reference Example 2, as an example of resin (A) (which is a raw material of polyamide microparticles), resin (A)-2 was synthesized. Specifically, in a 50°C oil bath, 2-pyrrolidone (127.7 g (1500 mmol)) and potassium tert-butoxide (3.37 g (30 mmol)) purified and water removed were added to a 500 mL flask to dissolve them uniformly. 1-acetyl-2-caprolactam (3.46 g (30 mmol)) was added as an initiator, and after nitrogen substitution in the system, polymerization was carried out for 24 hours to obtain a block. The obtained block was crushed, washed with ethanol, and vacuum dried at 80°C for 24 hours to obtain a 2-pyrrolidone polymer, resin (A)-2, having a melting point of 264°C, a crystallization temperature of 232°C, and a melt viscosity of 0.10 Pa·s.
[0306] <Reference Example 3>
[0307] In reference example 3, resin (A)-3 was synthesized as an example of resin (A) (which is a raw material of polyamide microparticles). Specifically, in a 50°C oil bath, 2-pyrrolidone (127.7 g (1500 mmol)) and potassium tert-butoxide (3.37 g (30 mmol)) purified and water removed were added to a 500 mL flask to dissolve them uniformly. 1-acetyl-2-caprolactam (2.30 g (20 mmol)) was added as an initiator, and after nitrogen substitution in the system, polymerization was performed for 72 hours to obtain a block. The obtained block was crushed, washed with ethanol, and vacuum dried at 80°C for 24 hours to obtain a 2-pyrrolidone polymer, resin (A)-3, having a melting point of 265°C, a crystallization temperature of 233°C, and a melt viscosity of 0.20 Pa·s.
[0308] <Reference Example 4>
[0309] In Reference Example 4, as an example of resin (A) (which is a raw material of polyamide microparticles), resin (A)-4 was synthesized. Specifically, in a 50°C oil bath, 2-pyrrolidone (102.1 g (1200 mmol)), ε-caprolactone (34.2 g (300 mmol)), and potassium tert-butoxide (3.37 g (30 mmol)) which had been purified and had water removed were added to a 500 mL flask and dissolved uniformly. 1-acetyl-2-caprolactam (3.46 g (30 mmol)) was added as an initiator, and after nitrogen substitution in the system, polymerization was performed for 4 hours to obtain a block. The obtained block was crushed, washed with ethanol, and vacuum dried at 80°C for 24 hours to obtain a 2-pyrrolidone / caprolactone copolymer, i.e., resin (A)-4, having a melting point of 193°C, a crystallization temperature of 170°C, and a melt viscosity of 0.03 Pa·s.
[0310] <Reference Example 5>
[0311] In Reference Example 5, as an example of resin (A) (which is a raw material of polyamide microparticles), resin (A)-5 was synthesized. Specifically, in a 50°C oil bath, 2-azetidinone (85.3 g (1500 mmol)), ε-caprolactone (34.2 g (300 mmol)), and potassium tert-butoxide (3.37 g (30 mmol)) which had been purified and water removed were added to a 500 mL flask and dissolved uniformly. 1-acetyl-2-caprolactam (3.46 g (30 mmol)) was added as an initiator, and after nitrogen substitution in the system, polymerization was performed for 10 hours to obtain a block. The obtained block was crushed, washed with ethanol, and vacuum dried at 80°C for 24 hours to obtain a 2-azetidinone / caprolactone copolymer, i.e., resin (A)-5, having a melting point of 272°C, a crystallization temperature of 240°C, and a melt viscosity of 0.06 Pa·s.
[0312] <Other items>
[0313] Other items used are as shown below.
[0314] (monomer)
[0315] 2-Pyrrolidone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), molecular weight 85.1
[0316] ·ε-Caprolactone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), molecular weight 114.1
[0317] ·2-Azetidinone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), molecular weight 71.1
[0318] 4-Aminobutyric acid (Fujifilm Wako Pure Chemical Industries, Ltd., special grade), 103.1
[0319] (catalyst)
[0320] Potassium tert-butoxide (produced by Tokyo Chemical Industry Co., Ltd.), molecular weight 112.2
[0321] (Initiator)
[0322] 1-Acetyl-2-caprolactam (manufactured by Tokyo Chemical Industry Co., Ltd.), molecular weight 115.2
[0323] 1-Acetyl-2-pyrrolidone (produced by Tokyo Chemical Industry Co., Ltd.), molecular weight 127.1
[0324] 1,3,5-Benzenetricarboxylic acid chloride (produced by Tokyo Chemical Industry Co., Ltd.), molecular weight 265.5
[0325] Palmitoyl chloride (produced by Tokyo Chemical Industry Co., Ltd.), molecular weight 274.9
[0326] (additive)
[0327] Irganox 1098 (registered trademark) (manufactured by BASF)
[0328] Lithium chloride (manufactured by Kanto Chemical Co., Ltd.), molecular weight 42.4
[0329] ·TAICROS (manufactured by Emantec Co., Ltd.)
[0330] In addition, as the resin (B) (which is a raw material of polyamide fine particles), the following resin (B)-1 and resin (B)-2 were used.
[0331] (Resin (B)-1)
[0332] Resin (B)-1 is polyethylene glycol manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. Resin (B)-1 is used by mixing a first molecular weight body having a weight average molecular weight of 6,000 (melt viscosity 0.15 Pa·s), a second molecular weight body having a weight average molecular weight of 20,000 (melt viscosity 0.78 Pa·s), and a third molecular weight body having a weight average molecular weight of 35,000 (melt viscosity 6.57 Pa·s) so as to obtain a desired melt viscosity.
[0333] (Resin (B)-2)
[0334] Resin (B)-2 is polyvinyl alcohol produced by Nippon Synthetic Chemical Industry Co., Ltd. The melting point of resin (B)-2 is 190°C, the saponification degree is 99.1%, and the melt viscosity is 0.52 Pa·s.
[0335] <Example 1>
[0336] In Example 1, polyamide microparticles were prepared using the resin (A)-1 of Reference Example 1 as the resin (A) and the resin (B)-1 as the resin (B). The resin (B)-1 was polyethylene glycol having a melt viscosity of 0.87 Pa·s. The melt viscosity ratio of the resin (A)-1 to the resin (B)-1 at 270° C. was 21.7.
[0337] Specifically, resin (A)-1 (36 g) and resin (B)-1 (36 g) were added to a SUS316 pressure-resistant container (hereinafter sometimes referred to as an autoclave) having a 100 mL reaction tank, and after nitrogen substitution in the system, the resins (A)-1 and (B)-1 were heated to 270° C. under nitrogen circulation, and melt-mixed for 30 minutes while stirring at 500 rpm using a stirring blade to form a polymer / polymer emulsion. After the melt-mixing of the resins (A)-1 and (B)-1, the molten mixture of the resins (A)-1 and (B)-1 was cooled to room temperature in the tank while continuing to circulate nitrogen. At this time, the temperature t 混合物 The time for maintaining in the temperature range higher than the crystallization temperature of resin (A)-1 and lower than the melting point of resin (A)-1 is 1 minute. Water (800 g) was added to the obtained molten mixture, heated to 80°C, and stirred for 1 hour. The obtained slurry was filtered, and water (800 g) was added to the screen material, heated to 80°C, and stirred and washed for 1 hour. Then, it was passed through a 200μm sieve to remove the agglomerates, and the obtained slurry was filtered again, and the separated screen material was dried at 80°C for 12 hours to obtain a powder (25.4 g). At this time, there were no agglomerates larger than 200μm. The results of the scanning electron microscope photograph of the obtained powder are shown in Figure 1 , 2 In Example 1, Figure 1 , 2 As shown, it was confirmed that polyamide fine particles were obtained.
[0338] The marine biodegradability of the polyamide microparticles of Example 1 was evaluated. As a result, it was found that the polyamide microparticles were decomposed by 30% one month after the start of the test. Therefore, the polyamide microparticles of Example 1 are marine biodegradable. Other characteristics and effects (evaluation results) of the polyamide microparticles of Example 1 are shown in Table 1 described below.
[0339] <Example 2>
[0340] In Example 2, polyamide microparticles were prepared and evaluated in the same manner as in Example 1 except that the mixing mass ratio of resin (A)-1 to resin (B)-1 during melt mixing was changed to 25:75. The properties and effects of the polyamide microparticles of Example 2 are shown in Table 1.
[0341] <Example 3>
[0342] In Example 3, polyamide microparticles were prepared and evaluated in the same manner as in Example 1 except that the mixing mass ratio of resin (A)-1 to resin (B)-1 during melt mixing was changed to 65:35. The properties and effects of the polyamide microparticles of Example 3 are shown in Table 1.
[0343] <Example 4>
[0344] In Example 4, polyamide microparticles were prepared and evaluated in the same manner as in Example 1 except that the mixing mass ratio of resin (A)-1 to resin (B)-1 during melt mixing was changed to 75:25. The properties and effects of the polyamide microparticles of Example 4 are shown in Table 1.
[0345] <Example 5>
[0346] In Example 5, polyamide microparticles were prepared and evaluated in the same manner as in Example 1, except that the resin (B)-1 used was changed to polyethylene glycol having a melt viscosity different from that in Example 1 (melt viscosity of 4.80 Pa·s, melt viscosity ratio to resin (A)-1 of 120). The properties and effects of the polyamide microparticles of Example 5 are shown in Table 1.
[0347] <Example 6>
[0348] In Example 6, polyamide microparticles were prepared and evaluated in the same manner as in Example 1, except that the resin (B)-1 used was changed to polyethylene glycol having a melt viscosity different from that in Example 1 (melt viscosity of 3.00 Pa·s, melt viscosity ratio to resin (A)-1 of 75.0). The properties and effects of the polyamide microparticles of Example 6 are shown in Table 1.
[0349] <Example 7>
[0350] In Example 7, polyamide microparticles were prepared and evaluated in the same manner as in Example 1, except that the resin (B)-1 used was changed to polyethylene glycol having a melt viscosity different from that in Example 1 (melt viscosity of 2.00 Pa·s, melt viscosity ratio to resin (A)-1 of 50.0). The properties and effects of the polyamide microparticles of Example 7 are shown in Table 1.
[0351] <Example 8>
[0352] In Example 8, polyamide microparticles were prepared and evaluated in the same manner as in Example 1, except that the resin (B)-1 used was changed to polyethylene glycol having a melt viscosity different from that in Example 1 (melt viscosity of 0.40 Pa·s, melt viscosity ratio to resin (A)-1 of 10.0). The properties and effects of the polyamide microparticles of Example 8 are shown in Table 1.
[0353] <Example 9>
[0354] In Example 9, polyamide microparticles were prepared and evaluated in the same manner as in Example 1, except that the resin (B)-1 used was changed to polyethylene glycol having a melt viscosity different from that in Example 1 (melt viscosity of 0.33 Pa·s, melt viscosity ratio to resin (A)-1 of 8.3). The properties and effects of the polyamide microparticles of Example 9 are shown in Table 2 described below.
[0355] <Example 10>
[0356] In Example 10, except that the resin used as the resin (A) was changed to the resin (A)-2 of Reference Example 2, polyamide microparticles were prepared and evaluated in the same manner as in Example 1.
[0357] Table 2 shows the properties and effects of the polyamide microparticles of Example 10.
[0358] <Example 11>
[0359] In Example 11, except that the resin used as the resin (A) was changed to the resin (A)-3 of Reference Example 3, polyamide microparticles were prepared and evaluated in the same manner as in Example 1.
[0360] Table 2 shows the properties and effects of the polyamide microparticles of Example 11.
[0361] <Example 12>
[0362] In Example 12, the polyamide microparticles were prepared and evaluated in the same manner as in Example 1, except that the resin used as resin (A) was changed to resin (A)-4 of Reference Example 4, and the temperature during melt mixing of resin (A)-4 and resin (B)-1 was changed to 200° C. In the evaluation of the marine biodegradability of the polyamide microparticles in Example 12, the polyamide microparticles were decomposed by 35% one month after the start of the test. Therefore, the polyamide microparticles of Example 12 are marine biodegradable. Other characteristics and effects of the polyamide microparticles of Example 12 are shown in Table 2.
[0363] <Example 13>
[0364] In Example 13, the washing (stirring and washing of the oversize with water) in Example 1 was not performed, the slurry obtained after melt mixing was filtered, and the separated oversize was dried at 80° C. for 12 hours. Polyamide microparticles were prepared and evaluated in the same manner as in Example 1. The characteristics and effects of the polyamide microparticles of Example 13 are shown in Table 2.
[0365] <Example 14>
[0366] In Example 14, polyamide microparticles were prepared and evaluated by the same method as in Example 1 except that 0.36 g of Irganox 1098 was added as an additive during melt mixing. In the evaluation of the marine biodegradability of the polyamide microparticles in Example 14, the polyamide microparticles were decomposed by 28% one month after the start of the test. Therefore, the polyamide microparticles of Example 14 have marine biodegradability. Other characteristics and effects of the polyamide microparticles of Example 14 are shown in Table 2.
[0367] <Example 15>
[0368] In Example 15, polyamide microparticles were prepared and evaluated by the same method as in Example 1 except that 0.36 g of lithium chloride was added as an additive during melt mixing. In the evaluation of the marine biodegradability of the polyamide microparticles in Example 15, the polyamide microparticles were decomposed by 30% one month after the start of the test. Therefore, the polyamide microparticles of Example 15 have marine biodegradability. Other characteristics and effects of the polyamide microparticles of Example 15 are shown in Table 2.
[0369] <Example 16>
[0370] In Example 16, polyamide microparticles were prepared and evaluated by the same method as in Example 1 except that 0.29 g of TAICROS was added as an additive during melt mixing. In the evaluation of the marine biodegradability of the polyamide microparticles in Example 16, the polyamide microparticles were decomposed by 20% one month after the start of the test. Therefore, the polyamide microparticles of Example 16 have marine biodegradability. Other characteristics and effects of the polyamide microparticles of Example 16 are shown in Table 2.
[0371] <Example 17>
[0372] In Example 17, polyamide microparticles were prepared and evaluated in the same manner as in Example 1, except that the resin used as resin (A) was changed to resin (A)-5 of Reference Example 5 and the temperature during melt mixing of resin (A)-5 and resin (B)-1 was changed to 280° C. The properties and effects of the polyamide microparticles of Example 17 are shown in Table 2.
[0373] <Example 18>
[0374] In Example 18, polyamide microparticles were prepared and evaluated in the same manner as in Example 1, except that the amount of water used as the washing solution was changed from a total of 1600 g to a total of 400 g. Table 2 shows the characteristics and effects of the polyamide microparticles of Example 18.
[0375] <Example 19>
[0376] In Example 19, polyamide microparticles were prepared and evaluated in the same manner as in Example 1, except that the amount of water used as the washing solution was changed from a total of 1600 g to a total of 800 g. Table 2 shows the properties and effects of the polyamide microparticles of Example 19.
[0377] <Example 20>
[0378] In Example 20, polyamide microparticles were prepared and evaluated in the same manner as in Example 1 except that the amount of water used as the washing solution was changed from a total of 1600 g to a total of 1200 g. Table 2 shows the properties and effects of the polyamide microparticles of Example 20.
[0379] <Example 21>
[0380] In Example 21, polyamide microparticles were prepared using the resin (A)-1 of Reference Example 1 as the resin (A) and the resin (B)-1 as the resin (B). The resin (B)-1 was polyethylene glycol having a melt viscosity of 0.87 Pa·s. The melt viscosity ratio of the resin (A)-1 to the resin (B)-1 at 270° C. was 21.7.
[0381] Specifically, resin (A)-1 (36 g) and resin (B)-1 (36 g) were added to a SUS316 autoclave having a 100 mL reaction tank, and after nitrogen substitution in the system, the temperature of these resins (A)-1 and resin (B)-1 was raised from room temperature to 270° C. under nitrogen circulation, and melt-mixed for 30 minutes while stirring at 500 rpm using a stirring blade, thereby forming a polymer / polymer emulsion. After the melt-mixing of resin (A)-1 and resin (B)-1, the temperature t of the molten mixture of these resins (A)-1 and resin (B)-1 was raised while continuing to circulate nitrogen. 混合物 Keep the temperature at 237°C (which is the melting point of resin (A)-1 + 5°C). 混合物The time kept in the temperature range higher than the crystallization temperature of resin (A)-1 and lower than the melting point of resin (A)-1 is 60 minutes. Then, the above molten mixture is discharged into a container filled with water (800g), cooled to room temperature, and then heated to 80°C again and stirred for 1 hour. The obtained slurry liquid is filtered, and water (800g) is added to the screen material, heated to 80°C, and stirred and washed for 1 hour. Then, it is passed through a 200μm sieve to remove the agglomerates, and the obtained slurry liquid is filtered again, and the separated screen material is dried at 80°C for 12 hours to obtain a powder (25.4g). At this time, there are no agglomerates larger than 200μm. The results of the scanning electron microscope photograph of the obtained powder are shown in Figure 3 , 4 In Example 21, Figure 3 , 4 As shown, it was confirmed that polyamide fine particles were obtained.
[0382] The polyamide fine particles of Example 21 obtained as described above were evaluated for marine biodegradability, etc. The characteristics and effects of the polyamide fine particles of Example 21 are shown in Table 3 described below.
[0383] <Example 22>
[0384] In Example 22, the resin used as resin (A) was changed to resin (A)-3 of Reference Example 3, and the mixing mass ratio of resin (A)-3 to resin (B)-1 during melt mixing was changed to 70:30. Polyamide microparticles were prepared and evaluated in the same manner as in Example 21. The properties and effects of the polyamide microparticles of Example 22 are shown in Table 3.
[0385] <Example 23>
[0386] In Example 23, the resin (B)-1 used was changed to polyethylene glycol having a melt viscosity different from that of Example 21 (melt viscosity of 3.00 Pa·s, melt viscosity ratio of resin (A)-1 to resin (B)-1 of 75.0), the mixing mass ratio of resin (A)-1 to resin (B)-1 during melt mixing was changed to 30:70, the temperature during melt mixing of resin (A)-1 and resin (B)-1 was changed to 280° C., and the temperature t of the molten mixture of resin (A)-1 and resin (B)-1 was set to 100° C. 混合物 Polyamide microparticles were prepared and evaluated in the same manner as in Example 21 except that the holding time in the temperature range higher than the crystallization temperature of resin (A)-1 and lower than the melting point of resin (A)-1 was changed to 90 minutes. The properties and effects of the polyamide microparticles of Example 23 are shown in Table 3.
[0387] <Example 24>
[0388] In Example 24, the temperature of the molten mixture is 混合物 Polyamide microparticles were prepared and evaluated in the same manner as in Example 22 except that the holding time in the temperature range higher than the crystallization temperature of resin (A)-3 and lower than the melting point of resin (A)-3 was changed to 90 minutes. The properties and effects of the polyamide microparticles of Example 24 are shown in Table 3.
[0389] <Example 25>
[0390] In Example 25, the resin used as resin (A) was changed to resin (A)-2 of Reference Example 2, and the mixing mass ratio of resin (A)-2 to resin (B)-1 during melt mixing was changed to 65:35. Polyamide microparticles were prepared and evaluated in the same manner as in Example 21. The properties and effects of the polyamide microparticles of Example 25 are shown in Table 3.
[0391] <Example 26>
[0392] In Example 26, the temperature of the molten mixture is 混合物 Polyamide microparticles were prepared and evaluated in the same manner as in Example 21 except that the holding time in the temperature range higher than the crystallization temperature of resin (A)-1 and lower than the melting point of resin (A)-1 was changed to 150 minutes. The properties and effects of the polyamide microparticles of Example 26 are shown in Table 3.
[0393] <Example 27>
[0394] In Example 27, the temperature of the molten mixture is 混合物 Polyamide microparticles were prepared and evaluated in the same manner as in Example 22 except that the holding time in the temperature range higher than the crystallization temperature of resin (A)-3 and lower than the melting point of resin (A)-3 was changed to 30 minutes. The properties and effects of the polyamide microparticles of Example 27 are shown in Table 3.
[0395] <Example 28>
[0396] In Example 28, the temperature of the molten mixture is 混合物 Polyamide microparticles were prepared and evaluated in the same manner as in Example 21 except that the holding time in the temperature range higher than the crystallization temperature of resin (A)-1 and lower than the melting point of resin (A)-1 was changed to 30 minutes. The properties and effects of the polyamide microparticles of Example 28 are shown in Table 3.
[0397] <Example 29>
[0398] In Example 29, the temperature of the molten mixture is 混合物 Polyamide microparticles were prepared and evaluated in the same manner as in Example 23 except that the holding time in the temperature range higher than the crystallization temperature of resin (A)-1 and lower than the melting point of resin (A)-1 was changed to 30 minutes. The properties and effects of the polyamide microparticles of Example 29 are shown in Table 3.
[0399] <Example 30>
[0400] In Example 30, the temperature of the molten mixture is 混合物 Polyamide microparticles were prepared and evaluated in the same manner as in Example 22 except that the holding time in the temperature range higher than the crystallization temperature of resin (A)-3 and lower than the melting point of resin (A)-3 was changed to 180 minutes. The properties and effects of the polyamide microparticles of Example 30 are shown in Table 3.
[0401] <Example 31>
[0402] In Example 31, the temperature of the molten mixture is 混合物 Polyamide microparticles were prepared and evaluated in the same manner as in Example 23 except that the holding time in the temperature range higher than the crystallization temperature of resin (A)-1 and lower than the melting point of resin (A)-1 was changed to 45 minutes. The properties and effects of the polyamide microparticles of Example 31 are shown in Table 3.
[0403] <Example 32>
[0404] In Example 32, the temperature of the molten mixture is 混合物 Polyamide microparticles were prepared and evaluated in the same manner as in Example 22 except that the holding time in the temperature range higher than the crystallization temperature of resin (A)-3 and lower than the melting point of resin (A)-3 was changed to 300 minutes. The properties and effects of the polyamide microparticles of Example 32 are shown in Table 3.
[0405] <Example 33>
[0406] In Example 33, the mixing mass ratio of resin (A)-3 and resin (B)-1 during melt mixing was changed to 75:25, and the temperature t 混合物 Polyamide microparticles were prepared and evaluated in the same manner as in Example 22 except that the holding time in the temperature range higher than the crystallization temperature of resin (A)-3 and lower than the melting point of resin (A)-3 was changed to 55 minutes. The properties and effects of the polyamide microparticles of Example 33 are shown in Table 4 described below.
[0407] <Example 34>
[0408] In Example 34, the resin (B)-1 used was changed to polyethylene glycol having a melt viscosity different from that of Example 21 (melt viscosity of 4.80 Pa·s, melt viscosity ratio of resin (A)-1 was 120), the mixing mass ratio of resin (A)-1 to resin (B)-1 during melt mixing was changed to 30:70, the temperature during melt mixing of resin (A)-1 and resin (B)-1 was changed to 280° C., and the temperature t of the molten mixture was adjusted to 100° C. 混合物 Polyamide microparticles were prepared and evaluated in the same manner as in Example 21 except that the holding time in the temperature range higher than the crystallization temperature of resin (A)-1 and lower than the melting point of resin (A)-1 was changed to 110 minutes. The properties and effects of the polyamide microparticles of Example 34 are shown in Table 4.
[0409] <Example 35>
[0410] In Example 35, polyamide microparticles were prepared and evaluated in the same manner as in Example 21, except that the resin (B)-1 used was changed to polyethylene glycol having a melt viscosity different from that of Example 21 (melt viscosity of 3.00 Pa·s, melt viscosity ratio to resin (A)-1 of 75.0). The properties and effects of the polyamide microparticles of Example 35 are shown in Table 4.
[0411] <Example 36>
[0412] In Example 36, polyamide microparticles were prepared and evaluated in the same manner as in Example 21, except that the resin (B)-1 used was changed to polyethylene glycol having a melt viscosity different from that in Example 21 (melt viscosity of 0.40 Pa·s, melt viscosity ratio to resin (A)-1 of 10.0). The properties and effects of the polyamide microparticles of Example 36 are shown in Table 4.
[0413] <Example 37>
[0414] In Example 37, except that the resin used as the resin (A) was changed to the resin (A)-2 of Reference Example 2, polyamide microparticles were prepared and evaluated in the same manner as in Example 21.
[0415] Table 4 shows the properties and effects of the polyamide microparticles of Example 37.
[0416] <Example 38>
[0417] In Example 38, polyamide microparticles were prepared and evaluated in the same manner as in Example 21 except that the mixing mass ratio of resin (A)-1 to resin (B)-1 during melt mixing was changed to 70:30. The properties and effects of the polyamide microparticles of Example 38 are shown in Table 4.
[0418] <Example 39>
[0419] In Example 39, polyamide microparticles were prepared and evaluated in the same manner as in Example 21 except that the mixing mass ratio of resin (A)-1 to resin (B)-1 during melt mixing was changed to 30:70. The properties and effects of the polyamide microparticles of Example 39 are shown in Table 4.
[0420] <Example 40>
[0421] In Example 40, polyamide microparticles were prepared and evaluated in the same manner as in Example 21 except that the temperature during melt mixing of resin (A)-1 and resin (B)-1 was changed to 264° C. Table 4 shows the properties and effects of the polyamide microparticles of Example 40.
[0422] <Example 41>
[0423] In Example 41, polyamide microparticles were prepared and evaluated in the same manner as in Example 21 except that the amount of water used as the washing solution was changed from a total of 1,600 g to a total of 400 g. Table 4 shows the characteristics and effects of the polyamide microparticles of Example 41.
[0424] <Example 42>
[0425] In Example 42, polyamide microparticles were prepared and evaluated in the same manner as in Example 21 except that the amount of water used as the washing solution was changed from a total of 1,600 g to a total of 1,200 g. Table 4 shows the characteristics and effects of the polyamide microparticles of Example 42.
[0426] <Comparative Example 1>
[0427] In Comparative Example 1, as the resin (B), resin (B)-1, which is polyethylene glycol having a weight average molecular weight of 20,000, was used, and polyamide microparticles were prepared using a resin different from the resin (A). Specifically, 4-aminobutyric acid (4 g), the resin (B)-1 (6 g), and water (10 g) as a solvent were added to a 100 mL autoclave, which was sealed and replaced with nitrogen to 10 kg / cm 2 While releasing nitrogen, adjust the pressure in the system to 0.1 kg / cm 2Then, the temperature was raised to 240°C. At this time, the pressure in the system reached 10 kg / cm 2 After that, the pressure was maintained at 10 kg / cm 2 After the temperature reaches 240°C, the water vapor is slightly depressurized at 0.2 kg / cm 2 The pressure was released at a rate of 1.5 1 / min and polymerization started. At this point, the solution inside was uniform and transparent. While the temperature was raised to 255°C, the pressure in the system was reduced to 0 kg / cm 2 , the pressure in the system becomes 0kg / cm 2 While nitrogen was flowing for 1 hour, heating was maintained to complete the polymerization. It should be noted that after the polymerization, the internal solution was suspended. Nitrogen was refilled to 10 kg / cm 2 After that, it was cooled to room temperature. Water was added to the obtained solid matter, and the solid matter was heated to 80°C to dissolve the dissolved matter. The obtained slurry was filtered, and water (40 g) was added to the sieve material, and it was washed at 80°C. Then, it was passed through a 200 μm sieve to remove the coagulant, and the obtained slurry was filtered again, and the separated sieve material was dried at 80°C for 12 hours to obtain polyamide microparticles.
[0428] The polyamide fine particles of Comparative Example 1 obtained as described above were evaluated in the same manner as in Example 1. The characteristics and effects of the polyamide fine particles of Comparative Example 1 are shown in Table 5 described below.
[0429] <Comparative Example 2>
[0430] In Comparative Example 2, pure water and the resin (A)-1 of Reference Example 1 were added to a 1L autoclave in such a manner that the concentration of the resin (A)-1 relative to the pure water was 1% by weight, and the autoclave was heated to an internal temperature of 150°C, thereby dissolving the resin (A)-1 in the hot water. After the heating was completed, the temperature of the hot water was maintained for 30 minutes, and then the hot water was cooled until the hot water reached room temperature, thereby obtaining a suspension solution in which particles of the resin (A)-1 were dispersed in pure water. Furthermore, the suspension solution was filtered with filter paper, and the substance retained on the filter paper was vacuum dried at 80°C for 8 hours, and as a result, polyamide particles of Comparative Example 2 were obtained. The polyamide particles of Comparative Example 2 obtained in this way were evaluated in the same manner as in Example 1. The characteristics and effects of the polyamide particles of Comparative Example 2 are shown in Table 5.
[0431] <Comparative Example 3>
[0432] In Comparative Example 3, 2-pyrrolidone (21.3 g (0.25 mol)) purified to remove water and potassium tert-butoxide (0.346 g (3 mmol)) were added to a flask attached to a decompression apparatus, and potassium tert-butoxide (hereinafter referred to as "catalyst") was reacted by heating at 50° C. under reduced pressure. As a result, a mixture of 2-pyrrolidone and a potassium salt of 2-pyrrolidone as a basic polymerization catalyst was obtained.
[0433] The reaction tank of the autoclave containing the raw material addition tank and the 100mL reaction tank was filled with the mixture obtained above (5.98 g), and 1-acetyl-2-pyrrolidone (0.18 g) was filled in the addition tank. Next, carbon dioxide was filled in the reaction tank until the internal pressure became 6 MPa, the internal temperature was made 40°C, the above mixture was melted, and then 1-acetyl-2-pyrrolidone was supplied from the addition tank. Then, the pressure was further increased to 30 MPa, and the polymerization reaction of 2-pyrrolidone was carried out in the reaction tank for 120 minutes. After the reaction was completed, the pressure was released, refilled (until 30 MPa), and after the pressure was released again, the microparticles were taken out, washed with water, and dried, thereby obtaining the polyamide microparticles of Comparative Example 3. The polyamide microparticles of Comparative Example 3 obtained in this way were evaluated in the same way as in Example 1. The characteristics and effects of the polyamide microparticles of Comparative Example 3 are shown in Table 5.
[0434] <Comparative Example 4>
[0435] In Comparative Example 4, 2-pyrrolidone 4 (2.55 g (500 mmol)), 2-pyrrolidone solution containing 24.3% of sodium salt of 2-pyrrolidone (7.93 g (18 mmol as sodium salt of 2-pyrrolidone)), and dehydrated hexane (50 g) were added to a 500 mL flask, and 1,3,5-benzenetricarboxylic acid chloride (0.27 g (1.0 mmol)) and palmitoyl chloride (1.64 g (6.0 mmol)) were added during stirring, and the mixture was stirred at 50° C. for 8 hours and allowed to stand overnight at room temperature. The reaction solution was filtered, washed with methanol and tetrahydrofuran, air-dried under a nitrogen stream, and dried under reduced pressure at 60° C. to obtain polyamide microparticles of Comparative Example 4. The polyamide microparticles of Comparative Example 4 obtained in this way were evaluated in the same manner as in Example 1. The characteristics and effects of the polyamide microparticles of Comparative Example 4 are shown in Table 5.
[0436] <Comparative Example 5>
[0437] In Comparative Example 5, polyamide microparticles were prepared in the same manner as in Example 1 except that the resin (B)-1 in Example 1 was changed to polypropylene glycol having a different melt viscosity (melt viscosity of 5.50 Pa·s, melt viscosity ratio to polyamide 4 (PA4) of 137.5). However, in Comparative Example 5, the emulsion particle size became too fine, and the polymer / polymer emulsion could not be stably maintained, so polyamide microparticles were not obtained.
[0438] <Comparative Example 6>
[0439] In Comparative Example 6, polyamide microparticles were prepared in the same manner as in Example 1 except that the resin (B)-1 in Example 1 was replaced with a polypropylene glycol having a different melt viscosity (melt viscosity of 0.15 Pa·s, melt viscosity ratio to PA4 of 3.8). However, in Comparative Example 6, the resin (A)-1 and the polypropylene glycol could not maintain equilibrium and could not form a polymer / polymer emulsion, so polyamide microparticles were not obtained.
[0440] <Comparative Example 7>
[0441] In Comparative Example 7, polyamide microparticles were prepared in the same manner as in Example 1 except that the mixing mass ratio of resin (A)-1 to resin (B)-1 during melt mixing was changed to 90:10. However, in Comparative Example 7, resin (A)-1 and resin (B)-1 could not maintain equilibrium and could not form a polymer / polymer emulsion, so polyamide microparticles were not obtained.
[0442] <Comparative Example 8>
[0443] In Comparative Example 8, polyamide microparticles were prepared in the same manner as in Example 1 except that the mixing mass ratio of resin (A)-1 to resin (B)-1 during melt mixing was changed to 10:90. However, in Comparative Example 8, phase inversion occurred, and polyamide microparticles were not obtained.
[0444] <Comparative Example 9>
[0445] In Comparative Example 9, polyamide microparticles were prepared in the same manner as in Example 1, except that the resin used as resin (B) was changed to the above-mentioned polyvinyl alcohol resin (B)-2 (melt viscosity of 0.52 Pa·s, melt viscosity ratio to resin (A)-1 of 13.0). However, the interfacial tension and melt viscosity of resin (A)-1 and resin (B)-2 were not balanced, and polyamide microparticles were not obtained.
[0446] <Comparative Example 10>
[0447] In Comparative Example 10, polyamide microparticles were produced in the same manner as in Example 21, except that the resin used as resin (B) was changed to the above-mentioned polyvinyl alcohol resin (B)-2 (melt viscosity of 0.52 Pa·s, melt viscosity ratio to resin (A)-1 of 13.0). However, the interfacial tension and melt viscosity between resin (A)-1 and resin (B)-2 were not balanced, and polyamide microparticles were not obtained.
[0448] <Comparative Example 11>
[0449] In Comparative Example 11, polyamide microparticles were produced in the same manner as in Example 21 except that the resin (A)-1 and the resin (B)-1 were placed in an autoclave heated to 200° C. However, the interfacial tension and melt viscosity of the resin (A)-1 and the resin (B)-1 were not balanced, and polyamide microparticles were not obtained.
[0450] <Comparative Example 12>
[0451] In Comparative Example 12, the temperature of the molten mixture was set to 混合物 Polyamide microparticles were prepared and evaluated in the same manner as in Example 22 except that the holding time in the temperature range higher than the crystallization temperature of resin (A)-3 and lower than the melting point of resin (A)-3 was changed to 20 minutes. The properties and effects of the polyamide microparticles of Comparative Example 12 are shown in Table 5.
[0452] <Comparative Example 13>
[0453] In Comparative Example 13, the temperature of the molten mixture was set to 混合物 Polyamide microparticles were prepared and evaluated in the same manner as in Example 21 except that the holding time in the temperature range higher than the crystallization temperature of resin (A)-1 and lower than the melting point of resin (A)-1 was changed to 20 minutes. The properties and effects of the polyamide microparticles of Comparative Example 13 are shown in Table 5.
[0454] <Comparative Example 14>
[0455] In Comparative Example 14, the temperature of the molten mixture was set to 混合物 Polyamide microparticles were prepared and evaluated in the same manner as in Example 23 except that the holding time in the temperature range higher than the crystallization temperature of resin (A)-1 and lower than the melting point of resin (A)-1 was changed to 20 minutes. The properties and effects of the polyamide microparticles of Comparative Example 14 are shown in Table 5.
[0456] <Comparative Example 15>
[0457] In Comparative Example 15, polyamide microparticles were prepared and evaluated in the same manner as in Example 21 except that the temperature during melt mixing of resin (A)-1 and resin (B)-1 was changed to 290° C. Table 5 shows the properties and effects of the polyamide microparticles of Comparative Example 15.
[0458] [Table 1]
[0459]
[0460] [Table 2]
[0461]
[0462] [Table 3]
[0463]
[0464] [Table 4]
[0465]
[0466] [Table 5]
[0467]
[0468] Industrial Availability
[0469] As described above, the polyamide microparticles and the method for producing the same according to the present invention are suitable for achieving polyamide microparticles having small average variation in the coefficient of kinetic friction when the microparticles are rubbed against each other and small average variation in the coefficient of kinetic friction after a certain period of time and having marine biodegradability.
Claims
1. A polyamide microparticle, characterized in that: The ratio of voids to the particle surface r and the specific surface area of the particle surface measured by the BET method, i.e., the BET specific surface area A BET Ratio r / A BET is 6.0 or more and 100.0 or less, and the BET specific surface area A BET The unit is m 2 / g, The polyamide microparticles are made of a polymer or copolymer having a repeating structural unit represented by the following chemical formula (1) as a main component, In the chemical formula (1), x is an integer of 2 or more and 3 or less.
2. The polyamide microparticles according to claim 1, characterized in that The BET specific surface area A BET 0.8m 2 / g or more and 5.0m 2 / g or less.
3. The polyamide microparticles according to claim 1 or 2, characterized in that: The sphericity is 90 or more.
4. The polyamide microparticles according to claim 1 or 2, characterized in that The impurity content is 0.50 wt% or less.
5. The polyamide microparticles according to claim 1 or 2, characterized in that: The volume average particle size is 0.1 μm or more and 100 μm or less.
6. The polyamide microparticles according to claim 5, characterized in that The volume average particle size is 0.1 μm or more and 30 μm or less.
7. The polyamide microparticles according to claim 1 or 2, characterized in that: The standard deviation of sphericity is 2.00 or less.
8. The polyamide microparticles according to claim 1 or 2, characterized in that: In the chemical formula (1), x is 3.
9. The polyamide microparticles according to claim 1 or 2, characterized in that: The temporal stability index is calculated by the following mathematical formula and is 0.60 or more. The temporal stability index is an index indicating the stability with respect to the decrease in the touch of the polyamide microparticles after continuous friction over time. Time stability index = 1 / (standard deviation of sphericity × (1 + impurity content)) In the mathematical formula, the standard deviation of sphericity is the standard deviation of sphericity of the polyamide microparticles, and the impurity content is the impurity content of the polyamide microparticles.
10. A method for producing polyamide microparticles, characterized in that: The invention relates to a method for producing polyamide microparticles using resin (A) and resin (B) as raw materials, wherein the resin (A) is a polymer or copolymer having a repeating structural unit represented by the following chemical formula (1) as a main component, and the resin (B) is an emulsion-forming resin capable of forming an emulsion with the resin (A) in a molten state, and the production method comprises the following steps: an emulsion forming step of melt-mixing the resin (A) and the resin (B) at a melting temperature not lower than their respective melting points to form an emulsion in which particles of the resin (A) are dispersed in the resin (B); a fixing step of cooling the molten mixture of the resin (A) and the resin (B) forming the emulsion to a temperature below the crystallization temperature of the resin (A) to fix the emulsion; and a recovery step of washing away the resin (B) with a washing solution that is a non-solvent for the resin (A) to recover polyamide microparticles made of the resin (A); In the production method, the melt viscosity ratio of the resin (A) to the resin (B) at 270° C. is 4.3 or more and 125.0 or less, In the chemical formula (1), x is an integer of 2 or more and 3 or less, The emulsion forming step includes a heating step of heating the resin (A) and the resin (B) from room temperature to the melting temperature. In the emulsion forming step, the resin (A) and the resin (B) are melted and mixed at the melting temperature of the resin (A) + 5°C or more and 280°C or less. The immobilization process comprises the following steps: a maintaining step of maintaining the temperature of the molten mixture in a temperature range higher than the crystallization temperature of the resin (A) and lower than the melting point of the resin (A); and a cooling step of cooling the temperature of the molten mixture after being maintained in the temperature range to a temperature below the crystallization temperature of the resin (A); In the maintaining step, the temperature of the molten mixture is maintained within the temperature range for 30 minutes to 10 hours.
11. A method for producing polyamide microparticles, characterized in that: The invention relates to a method for producing polyamide microparticles using resin (A) and resin (B) as raw materials, wherein the resin (A) is a polymer or copolymer having a repeating structural unit represented by the following chemical formula (1) as a main component, and the resin (B) is an emulsion-forming resin capable of forming an emulsion with the resin (A) in a molten state, and the production method comprises the following steps: an emulsion forming step of melt-mixing the resin (A) and the resin (B) at a melting temperature not lower than their respective melting points to form an emulsion in which particles of the resin (A) are dispersed in the resin (B); a fixing step of cooling the molten mixture of the resin (A) and the resin (B) forming the emulsion to a temperature below the crystallization temperature of the resin (A) to fix the emulsion; and a recovery step of washing away the resin (B) with a washing solution that is a non-solvent for the resin (A) to recover polyamide microparticles made of the resin (A); In the production method, the melt viscosity ratio of the resin (A) to the resin (B) at 270° C. is 4.3 or more and 125.0 or less, In the chemical formula (1), x is an integer of 2 or more and 3 or less, The emulsion forming step includes a heating step of heating the resin (A) and the resin (B) from room temperature to the melting temperature. In the emulsion forming step, the resin (A) and the resin (B) are melted and mixed at the melting temperature of the resin (A) + 5°C or more and 280°C or less. The immobilization process comprises the following steps: a holding step of holding the temperature of the molten mixture in a temperature range higher than the crystallization temperature of the resin (A) and lower than the melting point of the resin (A) for 1 second or longer and 10 minutes or shorter; and The cooling step is to cool the temperature of the molten mixture after being maintained in the temperature range to a temperature lower than the crystallization temperature of the resin (A).
12. The method for producing polyamide microparticles according to claim 10 or 11, characterized in that: The resin (B) has a melt viscosity at 270° C. of 0.40 Pa·s or more and 5.00 Pa·s or less.
13. The method for producing polyamide microparticles according to claim 10 or 11, characterized in that: The resin (B) is polyethylene glycol.
14. Polyamide microparticles produced by the production method according to claim 11, characterized in that: The sphericity is 96 or more, and the polymer or copolymer is composed of a repeating structural unit represented by the following chemical formula (1) as a main component, In the chemical formula (1), x is an integer of 2 or more and 3 or less, The polyamide microparticles have an impurity content of 0.50 wt % or less.
15. The polyamide microparticles according to claim 14, characterized in that The specific surface area of the particle surface measured by the BET method is the BET specific surface area A BET 5.0m 2 / g or less.
16. The polyamide microparticles according to claim 14 or 15, characterized in that The volume average particle size is 0.1 μm or more and 100.0 μm or less.
17. The polyamide microparticles according to claim 14 or 15, characterized in that The standard deviation of sphericity is 2.00 or less.
18. The polyamide microparticles according to claim 14 or 15, characterized in that In the chemical formula (1), x is 3.
19. The polyamide microparticles according to claim 14 or 15, characterized in that The temporal stability index is calculated by the following mathematical formula and is 0.60 or more. The temporal stability index is an index indicating the stability with respect to the decrease in the touch of the polyamide microparticles after continuous friction over time. Time stability index = 1 / (standard deviation of sphericity × (1 + impurity content)) In the mathematical formula, the standard deviation of sphericity is the standard deviation of sphericity of the polyamide microparticles, and the impurity content is the impurity content of the polyamide microparticles.
20. The polyamide microparticles according to claim 16, characterized in that The volume average particle size is 0.1 μm or more and 30 μm or less.
Citation Information
Patent Citations
Polyamide fine particles
JP2020100846A
Polyamide fine particles, method for producing same, and polyamide fine particle composition
WO2017195705A1
Production method for polyamide-4 particles
WO2019069799A1
Polyamide particle and production method thereof
JP2016186068A
Particulate polyamide, and method for preparing the particulate polyamide
US20160272776A1